Complexation with β-cyclodextrin derivatives enhanced the bioavailability of quercetin through improving solubility and inhibiting recrystallization - Qiao Chen; Hai-Xia Xu; Ji-Guang Chen; Lin Dai; Bao-Geng Fu; Qing-Feng Zhang (Journal of Food Engineering, 2027)

Metformin sensitizes endometriosis to medroxyprogesterone acetate treatment through MIG-6 mediated signaling - Guanwen Gao; Lvfang Duan; Fanyue Zhu; Wenkui Dai; Lina Geng; Degao Liu; Jinju Lin; Huashan Zhao; Yunfei Wang; Changzhong Li (Journal of Molecular Medicine, 2026)

Novel biallelic LSS variants in autosomal recessive hypotrichosis simplex: insights from a multi-omics approach - Xiaxia Liu; Kai Liu; Yuda Wei; Yongzhen Qi; Yangyang Luo; Tingli Chen; Xiaohua Ye; Junxu Lu; Yunjia Li; Liangqian Jiang; Juan Teng; Xingzhu Geng; et al. (Human Genetics, 2026)

Cadmium exposure activates ferroptosis through downregulated PPARγ expression in preeclampsia placenta - Xuemeng Li; Yumin Wu; Ziyan Zhao; Yangchen Wang; Mengqing Li; Yiding Geng; Jiancai Yin; Weilong Lin; Huiru Cheng; Baojing Zhao; Yuanyuan Yang; Zhen Yu (Toxicology, 2026)

Intensifying drought threatens the heat-regulating capacity of urban vegetation - Zixu Jia; Xiangzhong Guo; Tao Lin; Peng Wang; Junmao Zhang; Hongkai Geng; Yicheng Zheng; Yuan Chen; Jing Lin; Meixia Lin; Yuqin Liu (Landscape and Urban Planning, 2026)

Aligning green spaces with human activity: uncovering opportunity-realization mismatches in urban green exposure - Yicheng Zheng; Tao Lin; Nicholas A.S. Hamm; Yuan Chen; Tongyu Zhou; Xiangzhong Guo; Hongkai Geng; Matthew Ng; Hoon Han; Christopher Pettit; Yong-Guan Zhu (Landscape and Urban Planning, 2026)

Single-channel magnetotactile interface with structurally decoupled polarity–eigenfrequency encoding for in-plane sliding-direction decoding - Xiaojuan Hou; Shaowei Quan; Xin Zhang; Huipeng Zhao; Lin Shi; Fen Li; Wenping Geng; Jian He; Xiujian Chou (Chemical Engineering Journal, 2026)

Climate filtering of soil food webs drives divergent bottom-up and top-down regulation during grasslands recovery - Muhammad Ibrar; Meiqun Sheng; Yanbao Lei; Jie Shen; Xianzhi Deng; Juan Xue; Lin Liu; Igor Bogunovic; Geng Sun (Agriculture, Ecosystems & Environment, 2026)

Mechanism of Kushen Tongguan Pill on benign prostatic hyperplasia: roles of TLR4/NF-κB pathway and macrophage M1 polarization - Shaofeng Chen; Jie Wang; Yuhong Feng; Chunxu Li; Fu Wang; Lin Miao; Yaojun Li; Yangyang Lei; Qiang Geng; Zhong Li; Feng Zhao; Yuan Sun; et al. (Journal of Molecular Histology, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Targeted inhibition of JAK2 phosphorylation by GenX disrupts the JAK2-STAT3 pathway and induces cardiovascular toxicity in zebrafish: Insights from network toxicology and molecular dynamics - Yuzhi Zhao; Xiaoqiang Ge; Gaoyuan Wang; Qiaoling Zhang; Chengyu Geng; Zhongxiu Deng; Siyu Chen; Siyue Tan; Yifan Shi; Meng Zhao; Xinyi Wu; Shou-Lin Wang; et al. (Toxicology and Applied Pharmacology, 2026)

Modifying the gravity model based on heat flow patterns to reveal drivers of urban heat and cold corridor intensity - Ling Tao; Xin Zheng; Jianwei Geng; Qiuyue Zhao; Yuchen Lin; Ruiyun Dong; Kunyong Yu; Jian Liu (Sustainable Cities and Society, 2026)

Metabolic complementarity and enhanced biofilm formation drive the synergistic symbiosis of lactic acid bacteria and yeast in Tibetan kefir - Liangli Wu; Jianwei Zang; Luyao Xiao; Chang Xu; Xia Fan; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Tao Lin; Wei Li (International Dairy Journal, 2026)

Microbial diversity and technological characterization of lactic acid bacteria in traditional fermented yak dairy products from Huangnan Prefecture, Qinghai, China - Hongbo Li; Geng Long; Jiali Zhu; Lin Yang; Hongjuan Li; Jinghua Yu (International Dairy Journal, 2026)

Cryogenic ultrasound-assisted ethyl acetate extraction enables selective defatting of egg yolk powder with enhanced phospholipid retention and functionality - Shumin Chen; Xiaoyun Liu; Mohamed Salama; Xiaomeng Li; Lingzhuo Li; Haoyang Sun; Lin Deng; Pengfei Geng; Zehao Wu; Wei Wu; Zhaoxia Cai (Food Research International, 2026)

Engineering a uridine diphosphate galactosyltransferase PhUGT enables efficient whole-cell biosynthesis of hyperoside from quercetin - Mengjiao Li; Zhiwei Deng; Yu Geng; Lu Cai; Shan Lin; Yue Gao; Yijian Rao (Food Bioscience, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Thermal response analysis of permeable energy piles with different backfill materials under seepage conditions based on equivalent permeability characterization - Zhipeng Geng; Qiqi Wu; Jinli Lin; Xiang Li; Yongyi Li; Guoxiong Mei (Energy and Buildings, 2026)

Uncovering strain-induced mechanistic divergence of the oxygen evolution reaction on RuO2 - Guokang Han; Yuqi Yan; Dongyue Xin; Zhe Li; Xiaodan Wen; Jiannan Du; Lin Geng; Chunyu Du (Chemical Engineering Journal, 2026)

Cobalt oxide nanoparticles induce neurodevelopmental toxicity through ferritinophagy-mediated ferroptosis: Evidence from zebrafish and cell models - Shaozhuo Wang; Haojie Zhou; Siyue Tan; Chengyu Geng; Siyu Chen; Zhongxiu Deng; Yifan Shi; Meng Zhao; Yuzhi Zhao; Gaoyuan Wang; Qitong Yuan; Sirui Wang; et al. (Chemico-Biological Interactions, 2026)

Long-term variability of PM2.5 and its driving mechanisms in Xinjiang's Oasis Cities: insights from meteorological and anthropogenic heterogeneity - Wenyu Bai; Xueyan Zhao; Yingying Liu; Lijuan Wang; Wen Yang; Chunmei Geng; Weili Lin (Atmospheric Environment, 2026)

From fermentation to function: a critical review of lactic acid bacteria redesign for functional foods and precision nutrition - Jianwei Zang; Luyao Xiao; Xiaogan Zhao; Yibo Shi; Kai Ma; Changliang Zhang; Shuo Geng; Xin Rui; Tao Lin; Wei Li (Critical Reviews in Food Science and Nutrition, 2026)

Numerical Simulation Study on the Noise Reduction Mechanism of Biomimetic Microstructure Propellers - Xinge Geng; Weiguo Wu; Yongshui Lin (Journal of Marine Science and Engineering, 2026)
This study investigates the influence mechanism of biomimetic microstructures on propeller pressure fluctuations and radiated noise using numerical simulations. Based on the SST k-ω turbulence model and Lighthill’s acoustic analogy, the flow field and acoustic performance of propellers with and without microstructures are comparatively analyzed under different advance coefficients. Results show that microstructures arranged at the trailing edge optimize surface pressure distribution and promote a more uniform flow field. More importantly, they facilitate orderly vortex generation and shedding, reducing blade surface vortex intensity and suppressing flow-induced pressure fluctuations at the source. Acoustic analysis confirms that microstructures effectively reduce discrete noise at characteristic frequencies, with far-field maximum sound pressure level reductions of 5.94 dB at J = 0.5 and 3.11 dB at J = 1, while the noise directivity pattern is transformed from a “figure-of-eight” to a “heart-shaped” distribution. This study reveals the hydrodynamic mechanism of passive flow control for noise reduction via biomimetic microstructures, providing novel insights and theoretical foundations for low-noise propeller design and acoustic stealth technology development.

Assimilatory sulfate reduction potential in the plastisphere microbiome is linked to plastic mineralization in sulfur-rich mining-impacted river sediments - Tianle Kong; Zhili Du; Jianhua Zhou; Zhihao Zheng; Jian Zhang; Shui Zhang; Feng Jiang; Xiaoxu Sun; Wei Huang; Ruijian Zhang; Fangbai Li; Wenjie Lin; et al. (Water Research, 2026)

Soil organic carbon, soil heterotrophic respiration, and microbial community assembly in response to vegetation restoration in the karst area of Southwest China - Tongqing Su; Geng Lin; Dan Chen; Tingting Cui; Jianbing Zhang; Weiqun Luo; Baoqing Hu (Pedobiologia, 2026)

TiO2-x/WO3-x heterostructure memristor integrating self-powered photodetection and optoelectronic synaptic functions for spectrally responsive neuromorphic vision - Yonghui Lin; Chaoyang Hu; Lu Wang; Lun Zhong; Zhuohua Liu; Yurong Liu; Ruohe Yao; Yang Li; Kuiwei Geng (Chemical Engineering Journal, 2026)

Single-enzyme-level hierarchical nanohybrids enable spontaneous electron relay, robust enzyme stability, and one-pot sensor printing - Qichao Pan; Yue Lu; Qing Wu; Qingui Yang; Xingyin Zhou; Qingsong Sun; Shouyan Zhang; Wei Wu; Shuhua Zhang; Zhi Geng; Xun Sun; Lin Jia; et al. (Chemical Engineering Journal, 2026)

Integrated multi-omics analysis reveals mechanism of metabolic reprogramming enabling bacterial selenite detoxification and selenium nanoparticles biogenesis by Serratia marcescens HBQT - Yidong Zhang; Jin Lin; Mingyang He; Shiyao Li; Yan Liu; Hao Feng; Yawen Geng; Tao Li; Li Zhang; Jintao Xia; Taohong Zhou (Bioresource Technology, 2026)

Schizantherin B alleviates cisplatin-induced ototoxicity and does not interfere cisplatin-based chemotherapy in a breast cancer model - Zirui Zhao; Lei Han; Zhijiao Xu; Benyu Nan; Honghai Tang; Dingding Dong; Zhen Zen; Ziwen Gao; Cheng Ye; Xinsheng Huang; Jianning Zhang; Geng-Lin Li; et al. (Archives of Toxicology, 2026)

Contrasting responses of nematode food webs and energy flux to warming and nitrogen deposition between alpine meadow and steppe on the Tibetan Plateau - Juan Xue; Tahseen Saba; Yanbao Lei; Jie Shen; Kangshan Mao; Xianzhi Deng; Yuanjiang Yao; Lin Liu; Igor Bogunovic; Natasa Hulak; Armin Mesic; Geng Sun (Plant and Soil, 2026)

Amino Acid Metabolic Remodeling in Bivalves Under Environmental Stress: Roles, Mechanisms, and Implications for Bivalve Health—A Review - Yichen Lin; Wei Chen; Jixing Peng; Xinnan Zhao; Yan Di; Mengmeng Guo; Yanfang Zhao; Haiyan Wu; Guanchao Zheng; Qianqian Geng; Zhijun Tan (Fishes, 2026)
Climate change and increasing instability in coastal marine environments have intensified stressors such as elevated temperature, hypoxia, salinity variation, and pollutant exposure, posing major challenges to the survival, health, and culture performance of bivalves. As economically important aquaculture species and key components of coastal ecosystems, bivalves are highly sensitive to environmental fluctuations, making their metabolic responses highly relevant to both physiological adaptation and aquaculture sustainability. Increasing evidence indicates that metabolic remodeling is an important adaptive strategy supporting bivalve tolerance to environmental stress, with amino acid metabolic remodeling emerging as one of its most sensitive and functionally important components. This review summarizes the major response patterns, key pathways, and potential regulatory mechanisms of amino acid metabolism in bivalves under different stress conditions. Different environmental stressors induce distinct yet integrated shifts in amino acid metabolism, including enhanced catabolism, carbon–nitrogen redistribution, osmotic regulation, and antioxidant defense, thereby supporting energy homeostasis and physiological stress tolerance in bivalves. By highlighting amino acid metabolic remodeling as a central mechanism of bivalve adaptation to environmental stress, this review provides insights into adaptive responses, metabolite-based indicators for monitoring aquaculture environments and bivalve health, and management strategies for improving resilience in bivalve aquaculture.

Undescribed phenylspirodrimane dimers with anti-gouty activity from the coral-derived fungus Stachybotrys chartarum - Shuang Lin; Yi-Fan Geng; Hanxiao Zeng; Zixue Chai; Baolei Fan; Jun-Cheng Su; Yonghui Zhang; Zhengxi Hu (Phytochemistry, 2026)

Nonlinear coupled dynamic response of TLP wind turbine with redundant mooring under complex environmental loads and multi-tendon failures - Mingyang Wei; Jianhua Zhang; Ke Sun; Yian Chen; Zaibin Lin; Yan Geng; Hongwen Liu; Yanghua Ou (Ocean Engineering, 2026)

Improving spatiotemporal assessment of watershed soil redistribution by integrating source-sink theory into a multi-model framework - Rui Tan; Yu Tao; Geng Guo; Kaiwen Huang; Zicheng Liu; Lin Chen; Xin Liu; Jie Lin (Journal of Hydrology, 2026)

Alnustone ameliorates obesity and polycystic ovary syndrome by remodeling adipose metabolism via AMPK signaling - Yiming Qin; Shourui Hu; Yanqi Xu; Zongxuan Lin; Xiaofan Liang; Yue Liu; Yuxuan Li; Chunxuan Geng; Xiangyan Chen; Xizi Feng; Zi-Jiang Chen; Han Zhao; et al. (Science China Life Sciences, 2026)

Impacts of overlapping tunnels underpassing an existing overpass in water-rich sandy gravel strata - Geng Wang; Zhaoping Li; Zihan Zhao; Yi Zhao; Yuhang Lin (Innovative Infrastructure Solutions, 2026)

Corrigendum to “The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence” Aquaculture, Volume 622, 15 July 2026, 744082 - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

RHBDD2 Confers Insensitivity of Esophageal Squamous Cell Carcinoma to Cisplatin by Inhibiting Ferroptosis Through the Wnt3a/β-Catenin/FTH1 Axis - Youxiang Ding; Geng Tian; Minjie Zhang; Lin Zou (Cell Biochemistry and Biophysics, 2026)

The hemolysin-associated TH locus in Vibrio mimicus reprograms central metabolism and couples it to oxidative stress defense through iron acquisition to drive virulence - Jiao Wang; Kun Peng; Yilin Wang; Keyu Zhou; Jingyi Lin; ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture, 2026)

H3K18 lactylation-regulated ATG10 is involved in the acute respiratory distress syndrome induced by acute exposure to hydrogen sulfide through activation of autophagy in lung epithelial cells - Bingyu Ling; Ping Geng; Bowen Fan; Xiaolong Wu; Yi Yang; Jiaheng Lin; Wenjie Li; Qizhan Liu; Cheng Cheng; Jinsong Zhang; Hao Wu (Journal of Hazardous Materials, 2026)

Make more pixels usable: A data-driven framework for customizable cloud and shadow processing in satellite imagery - Yu Xia; Tianwu Lin; Xiangyu Liu; Shuang Chen; Shuai Yuan; Geng Tian; Yang Xu; Wei Zhang; Wei He; Jie Wang; Peng Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Lipid-driven modulation of milk/soy proteins digestion in young child formulas: From in vitro gastric emptying to intestinal absorption coupled with in vivo protease activation - Qiaoya Mo; Jiahui Wang; Chang Xu; Xia Fan; Tao Lin; Kai Ma; Changliang Zhang; Shuo Geng; Feng Ji; Xin Rui; Wei Li (Food Research International, 2026)

Climate and AM/EcM ratio jointly modulate species richness–biomass relationships in temperate forests - Yizhen Shao; Jianyou Li; Jiao Lin; Zhonghu Geng; Yazhou Feng; Geraldo Wilson Afonso Fernandes; Yun Chen; Zhiliang Yuan (Forest Ecology and Management, 2026)

Novel ACE-inhibitory peptides from egg yolk protein by stepwise enzymatic hydrolysis: Optimization, structural-activity characterization and molecular dynamics simulation - Haoyang Sun; Lin Deng; Xiaoyun Liu; Qishan Dong; Zuyue Li; Wei Hu; Lingzhuo Li; Pengfei Geng; Mohamed Salama; Heping Li; Zhaoxia Cai (Food Chemistry, 2026)

Novel winter crop integration enhances crop productivity, economic benefits, and their stability in tobacco-based paddy-upland rotations under climate-driven dynamics - Rentao Liao; Wenhua Dongchen; Zichao Mao; Caiqing Wang; Yongjun Xiong; Shaowu Geng; Chun Lin; Zhengjie Liu (Field Crops Research, 2026)

The biocontrol potential of Trichoderma asperellum M1 against kiwifruit soft rot caused by Botryosphaeria dothidea - Qing Tan; Jieyu Li; Qian Zhou; Chenlan Li; Ziqin Bai; Geng Liu; Jieping Lin; Hui Luo; Wei Xue (European Journal of Plant Pathology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Heading control of a multi-fin biomimetic robotic fish based on Q-learning enhanced central pattern generator (CPG) - Qiyang Zuo; Lin Liang; Xinyi Gao; Yiyang Li; Jiazi Geng; Zhengkun Yi; Feifei Zhang; Kai He; Fengran Xie (Ocean Engineering, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

The rising power of females: Dioecious shrub enhances soil organic carbon sequestration via fungal necromass in chronosequence of desertified alpine grassland restoration - Dongming Chen; Muhammad Ibrar; Fei Yan; Geng Sun; Ran Xue; Aomei Jia; Jiqiong Zhou; Yongheng Gao; Congyu Ma; Meng Wang; Jian Zhang; Zhouwen Ma; et al. (Journal of Environmental Management, 2026)

Microplastic entry into bloodstream via hemodialysis: A dual-simulation clinical study - Yao Deng; Taoping Sun; Zhenheng Long; Xiaoling Luo; Xuyang Geng; Zefang Lin; Chunzhao Chen; Xiaoliang Li (Environmental Pollution, 2026)

Bridging the gap between the actual and expected chiller power load variations in HVAC demand response: A dynamic modeling method considering the PID control characteristic - Xiaoyu Lin; Yuyang Zhao; Yihu Zhang; Yanxue Li; Hao Tang; Bin Zhu; Borong Lin; Yang Geng (Energy and Buildings, 2026)

Efficient DNA Extraction Coupled with Fluorescence Loop-Mediated Isothermal Amplification (LAMP) for On-Site Early Warning Detection of Vibrio parahaemolyticus - Fengyi Liu; Qilin Geng; Xue Sun; Jie Lin; Xuan Zhu; Danyang Wang; Xiao-Hua Zhang; Jingjie Hu; Shi Wang; Lisui Bao; Jia Lv (Marine Biotechnology, 2026)

Dynamic Analysis of Ecological Health Status of the Small Watersheds in Central Shandong, China Based on Remote Sensing Ecological Index and PCA - Xiuqin Sun; Qianxun Chen; Guangzhou Yu; Weijie Zhong; Feiyong Chen; Keqin Liu; Fengke Dou; Geng Xu; Lin Wang; Jin Wang (Journal of the Indian Society of Remote Sensing, 2026)

Ethylene-related gene regulation in rhododendrons under heat stress - Shida Xu; Fanyu Zeng; Xingmin Geng; Lingfeng Mao; Xiaoyue Lin (Horticulture, Environment, and Biotechnology, 2026)

Study on multiscale particle motion characteristics in hydraulic lifting pipe under pulsating flow conditions - Desheng Chen; Geng Li; Wenhao Sun; Yuanming Ding; Zhe Lin; Yanping Wang (Ocean Engineering, 2026)

Variation characteristics and segment differences of urban heat exposure risk in continuous time series: A comprehensive synchronous comparison of daily and hourly scales - Junmao Zhang; Xia Yao; Meixia Lin; Tao Lin; Yuan Chen; Wenhui Li; Hongkai Geng; Yicheng Zheng; Zixu Jia; Hong Ye; Guoqin Zhang (Landscape and Urban Planning, 2026)

Diverging vegetation phenology responses between urban cores and suburbs in 233 Chinese cities - Yuqin Liu; Yuan Chen; Tao Lin; Hongkai Geng; Guoqin Zhang; Yiyi Huang; Xin Cao; Meixia Lin; Junmao Zhang; Saiping Xu; Jiahua Zhang; Gerrit de Leeuw (Landscape and Urban Planning, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Structural determinants of gelation kinetics in rambutan seed starches: Implications for enhanced precision in 3D food printing - Rui He; Yuxuan Li; Xiaoyu Lin; Bo Xu; Xiang Huo; Weiming Zhang; Tao Yang; Geng Zhong; Fengwei Xie; Ying Chen (Carbohydrate Polymers, 2026)

Deep Learning-Based Monthly Runoff Simulation in Changing Environments: Enhancing Accuracy by Reducing Data Redundancy - Shenghong Liu; Ji Liu; Shaokang Yang; Zhenxin Bao; Shan-e-hyder Soomro; Wenjuan Chang; Qingxia Lin; Qirui Zhang; Gantao Yang; Ruilin Geng; Haiyu Wang; Longteng Dai (Water Resources Management, 2026)

Preparatory Activity Indexes Motor Memory in the Motor Cortex - Xiao–Lin Shen; He–Xin Zhao; Yu–Hao Xiao; Yong–Xiang Wang; Li–Zhang Zeng; Hong–Yan Geng (Neuroscience Bulletin, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Precise engineering and structural evolution of metallic silver nanoclusters - Lin Geng; Laurent Ruhlmann; Wei-Hui Fang (Science Bulletin, 2026)

Facile preparation and enhanced comprehensive performance of TFC nanofiltration membrane based on carboxylated graphene oxide/polyethersulfone substrate - Ying Ma; Anqi Liang; Fangbo Zhao; Chengbao Geng; Zhiguo Li; Liu Yang; Caixu Wang; Peng Lin; XiaoXiao Zhang (Journal of Environmental Chemical Engineering, 2026)

Intergenerational attitude–behavior linkages in household energy saving: Gender inequality perspective - Bo Hu; Wenqing Guan; Jiaci Lin; Liuna Geng (Journal of Environmental Management, 2026)

Unraveling geographical heterogeneity and spatial distribution of Long pepper fruits: An integrative analytical perspective - Shuwen Geng; Conghui Duan; Ying Ye; Yuye Gao; Yujia Zhai; Fangyuan Gao; Yuewei Ge; Yang Chen; Yunxia Li; Rongping Zhang; Xinglong Chen; Jian-lin Wu; et al. (Food Chemistry, 2026)

Synergistic high-flux desalination via multistage photothermal-electric coupling - Ruduan Yuan; Jiacheng Wang; Yuting He; Yang Geng; Jinshuai Wang; Meng Xia; Kaixin Wang; Jiaxin Luo; Zhaoyu Chen; Qinglin Zhang; Jingxuan Lin; Yuxi Yang; et al. (Desalination, 2026)

Estimating Human Jejunal Effective Permeability Using Numerical Deconvolution of Oral Solution Concentration Data - Wenqian Zhang; Jia Geng; Xingrui He; Hanxi Yi; Jie Dong; Lin Mei; Feifan Xie (Pharmaceutical Research, 2026)

Comparison of PM2.5 Pollution during Heating and Non-Heating Periods in Northwest China: Chemical Characteristics, Secondary Contribution, and Regional Transport - Linlin Liang; Xinze Geng; Feng Lin; Xiaoru Liu; Liping Ma; Kun Li; Leixiang Wu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu (Journal of Meteorological Research, 2026)

QSAR-enhanced machine learning for mechanistic insights and real-time prediction of DBPs in drinking water distribution systems - Dai-Xu Zhang; Tian-Yang Zhang; Zhen-Ning Luo; Zhu Peng; Zheng-Xiong Zheng; Yun-Qiao Zeng; Qi Fu; Ling Hu; Bing Geng; Chao-Yi Tong; Yu-Lin Tang; Bin Xu (Water Research, 2026)

Seismic behavior of caisson quay walls with fiber-reinforced calcareous sand backfill - Jie Tan; Lin Zhou; Feifan Ren; Xueyu Geng; Qiangqiang Huang; Chao Shen (Soil Dynamics and Earthquake Engineering, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Uncovering biases in standard occupancy assumptions using urban-scale mobile signaling data - Shuyi Chen; Yihu Zhang; Jun Xiao; Ziliang Wei; Yangyang Wang; Yixing Chen; Hao Zhou; Yang Geng; Borong Lin (Building and Environment, 2026)

Electrophysiological Characterization of Murine Vestibular Efferent Neurons and Modulation by Acute Peripheral Vestibular Deprivation - Jinyu Wang; Mengfan Xu; Lei Zhang; Wenjie Liu; Siyue Wang; Liqin Wang; Ning Cong; Geng-Lin Li; Jing Wang (Neuroscience Bulletin, 2026)
Vestibular efferent neurons in the brainstem provide direct cholinergic innervation to peripheral vestibular organs, thereby modulating their sensory responsiveness. In this study, a genetically targeted mouse model with choline acetyltransferase-driven fluorescent labeling enabled the precise localization of these neurons to the dorsolateral region of the genu of the facial nerve. Whole-cell patch-clamp recordings in acute brainstem slices revealed that virtually all neurons exhibited spontaneous action potential firing, with marked heterogeneity in discharge patterns and after-hyperpolarization kinetics. Prominent A-type potassium currents were identified and found to be differentially regulated by acetylcholine and calcitonin gene-related peptide. Acute unilateral vestibular deprivation induced a bilateral enhancement of spontaneous firing, indicating sensitivity to altered sensory input. These findings define the intrinsic electrophysiological properties and neuromodulatory mechanisms of vestibular efferent neurons, providing mechanistic insight into their roles in both physiological regulation and adaptive plasticity within the vestibular system.

PPIL1 promotes hepatocellular carcinoma progression and associates with poor prognosis - Yunyu Wu; Shuqing Jiang; Junming Yu; Hechun Lin; Saihua Zhang; Yizi Jin; Yang Su; Wenjiao Jin; Chao Ge; Qin Geng; Taoyang Chen; Jinjun Li; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Demonstration of biomass chemical looping gasification in a 5 MWth pilot unit using ilmenite as oxygen carrier - Zhenshan Li; Jiaye Li; Yang Wang; Weicheng Li; Geng Wei; XingLei Liu; Shanhu Lin; Qi Sun; Yongjia Yang; Angran Zhao; Hao Wang; Qingsong Meng; et al. (Fuel, 2026)

Integrating field surveys and visual interpretation to enhance CSLE model of soil erosion response to LUCC in Southwest China - Rui Tan; Geng Guo; Kaiwen Huang; Zicheng Liu; Chaorui Wang; Jie Lin; Yizhong Huang (Environmental Modelling & Software, 2026)

Ball Milling-Assisted Fabrication of Zirconium-Biochar-Zeolite Composites for Phosphate Removal in Aquatic Systems - Xiao Ling; Xinyu Qi; Wenshan Peng; Yapeng Liu; Cunguo Lin; Haiying Guo; Xiaoheng Geng (Water, Air, & Soil Pollution, 2026)

Seismic Fault Detection Using Interpretable Tree-Based Ensemble Models with Bayesian Optimization - Yang Li; Suping Peng; Xiaoqin Cui; Peng Lin; Dong Li; Tao He; Kunheng Li; Henggao Geng; Hongpeng Zhao (Pure and Applied Geophysics, 2026)

Multifaceted Role of RIMBP2 in Promoting Hearing in Murine Cochlear Hair Cells - Menghui Liao; Xin Chen; Ling Lu; Qing Liu; Rongrong Guo; Yuyang Qiu; Yangnan Hu; Yuhua Zhang; Qiaojun Fang; Panpan Zhang; Yige Li; Shuijin He; et al. (Neuroscience Bulletin, 2026)

Plant-soil synchrony and its role in the restoration of desertified grassland on the Qinghai-Tibet Plateau - Tahseen Saba; Qiujie Chen; Yanbao Lei; Jie Shen; Lin Liu; Geng Sun (Soil and Tillage Research, 2026)

Explainable deep learning combined attention-based LSTM for building energy prediction: a framework from the perspective of supply side - Muhammad Saad Ul Haq; Wenjie Ji; Xingyu Pei; Shuli Liu; Yang Geng; Borong Lin; Haider Ali (Energy and Buildings, 2026)

Oxygen carrying reactivity of ilmenites after long series of redox cycles in a 5 MWth CLC pilot unit - Yang Wang; Zhenshan Li; Dan Li; Jiaye Li; Chen Song; Qi Sun; Jinzhi Cai; Yongjia Yang; Hao Wang; Angran Zhao; Weicheng Li; Geng Wei; et al. (Chemical Engineering Journal, 2026)

Modeling of industrial biomass fluidized bed gasification system and optimization of operating conditions - Haodong Fan; Han Zhang; Geng Li; Xiong Zhang; Zixue Luo; Lin Huang; Shihong Zhang (Biomass and Bioenergy, 2026)

Exerkine-Mediated Regulation of the NLRP3 Inflammasome in Neuroprotection: Mechanistic Insights and the Role of Exercise - Shaokai Tang; Yuanwen Geng; Qinqin Lin; Zhenjun Tian (Molecular Neurobiology, 2026)

Enhanced El Niño–Southern Oscillation impact on Somali jet under greenhouse warming - Haodong Wang; Tao Geng; Wenju Cai; Shuo Wu; Xiaopei Lin (Climate Dynamics, 2026)

Microalgae-derived biodiesel: Review on microalgae species, genetic modification, cultivation strategies, and mutagenesis - Jing Tian; Jianqun Lin; Guoqiang Zhuang; Peiyao Sun; Pengxue Geng; Linxu Chen; Xianke Chen (Algal Research, 2026)

Advancing Non‐Contact Fish Phenotyping via Optical Sensing: Toward Precision Aquaculture - Kai Lin; Shiyu Zhang; Wei Wang; Tian Dong; Wen Ding; Chenfan Geng; Yihang Lu; Hongxia Hu (Reviews in Aquaculture, 2026)
Non‐contact fish phenotyping has become an essential strategy for precision aquaculture, enabling accurate, high‐throughput, and non‐invasive trait measurement. In this review, a digital phenotyping framework is summarized, including application‐driven trait definition, multimodal data acquisition (2D, 2.5D, and 3D imaging), and automated phenotypic analysis based on computer vision and deep learning. According to current research paradigms, optical phenotyping applications are systematically categorized into three major domains: morphological, behavioral, and appearance‐based phenotyping. Multimodal optical sensing systems now support high‐throughput morphological, behavioral, and appearance‐based phenotyping, enabling applications ranging from biomass estimation and intelligent feeding control to selective breeding, product quality evaluation, species identification, and disease diagnosis. Despite rapid methodological progress, most existing studies remain confined to laboratory or semi‐controlled environments, and large‐scale implementation in commercial production systems is still limited. Key challenges persist in underwater image degradation, posture‐induced measurement uncertainty, data heterogeneity, model generalizability, computational constraints, and the integration of phenotypic and genomic data for precision breeding. Finally, future development pathways are discussed, including efficient and flexible data acquisition platforms, lightweight and real‐time processing, transfer and few‐shot learning, multimodal data fusion, novel phenotype quantification, and standardized open datasets. Based on a comprehensive analysis of over 100 studies, this review maps the current technological landscape and proposes pathways toward scalable, intelligent phenotyping systems that can improve fish welfare, enhance breeding efficiency, and promote sustainable aquaculture management.

AFP-GFuse: an antifungal peptide identification model with structural information fusion via multi-graph neural networks and cross-attention mechanism - Xiaomeng Lin; Ruiqi Liu; Aoyun Geng; Junlin Xu; Yajie Meng; Feifei Cui; Leyi Wei; Quan Zou; Zilong Zhang (Molecular Diversity, 2025)

Study on the stability of the excavation face in parallel overlapping shield tunnels - Geng Wang; Yuhang Lin; Zhaoping Li; Zhijun Ye; Rucun Han (Tunnelling and Underground Space Technology, 2025)

Urban ecological risk assessment under water resources constraints: Framework development and application in Chinese cities - Zixu Jia; Tao Lin; Yuqin Liu; Hongkai Geng; Junmao Zhang; Yicheng Zheng; Xiangzhong Guo; Meixia Lin; Yuan Chen; Wenhui Liu; Jing Lin (Urban Climate, 2025)

Theoretical insights into tunnel portal dynamics: effects of SV waves on seismic partitioning and structural strain - Qi Wang; Song Wang; Yan Zhao; Ping Geng; Huoming Shen; Lin Deng (Soil Dynamics and Earthquake Engineering, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Analysis of the odor profile and metabolome of traditional sea cucumber dishes: Multi-omics combined screening for molecular regulatory targets of process - Jiahui Song; Qiang Geng; Huihui Wang; Xu Zhang; Jian Jiao; Songyi Lin (Food Chemistry, 2025)

Exploration of the multi-dimensional quality deterioration patterns and mechanism analysis of sea urchin gonads during storage at ambient temperature - Jiahui Song; Qiang Geng; Yue Tang; Dong Chen; Songyi Lin (Food Chemistry, 2025)

One-pot detection method for allergen gene-edited cow genotypes based on hair shaft samples - Wentao Geng; Shenghao Lin; Longjiao Zhu; Zaihui Du; Wentao Xu (Food Bioscience, 2025)

Fabrication and characterization of starch-based edible films loaded with Lactiplantibacillus plantarum STB9b for pork preservation - Jianwei Zang; Yue Hu; Tao Lin; Xia Fan; Yimeng Kou; Yibo Shi; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Xin Rui; Wei Li (Food Packaging and Shelf Life, 2025)

Flux measurements of NOx, O3 and Ox: Emission characteristics, inventory validation and titration effects - Xiaoxiao Zhang; Bin Yuan; Yibo Huangfu; Huizhi Liu; Thomas Karl; Ming Chang; Shiyi Chen; Tao Song; Jintai Lin; Guannan Geng; Hongjuan Li; Eran Tas (Environmental Pollution, 2025)

Boosting visible-light photocatalytic antibiotic degradation with g-C3N4 nanosheet-functionalized UiO-66-NH2(Hf) heterojunctions - Ting Liao; Zhiyong Lin; Yicheng Huang; Wentao Li; Kaixin Li; Zhihui Huang; Xinrui Zhao; Limin Geng (Chemical Engineering Journal, 2025)

ITZO/Ga2O3 heterostructure memristor with integrated optoelectronic synaptic function for neuromorphic vision applications - Yonghui Lin; Lun Zhong; Lu Wang; Yuxuan Nie; Fupeng Yang; Jianyong Pan; Yurong Liu; Ruohe Yao; Yang Li; Kuiwei Geng (Chemical Engineering Journal, 2025)

Parametric study of tunnel fault resistance using numerical modeling and orthogonal experiment for segmental lining design - Qi Wang; Yiying Chen; Song Wang; Ping Geng; Peisong Li; Huoming Shen; Lin Deng (Soil Dynamics and Earthquake Engineering, 2025)

Zoning effect on urban heat exposure risk: comparing four typical spatial zoning approaches - Junmao Zhang; Meixia Lin; Jiayi Fu; Yuan Wang; Tao Lin; Yuan Chen; Hongkai Geng; Zixu Jia; Yicheng Zheng; Xia Yao (Landscape and Urban Planning, 2025)

Unraveling hiatuses in black shales: Mechanisms and implications from the Lower Silurian Longmaxi Formation, South China - Yichen Liu; Benzhong Xian; Qianran Wu; Zhiyong Lu; Haocheng Shi; Mingjin Wu; Zhiyun Yu; Lin Zhao; Junyang Geng; Haiying Chen (International Journal of Coal Geology, 2025)

Focusing on the formation mechanism and foaming properties of casein-hyaluronic acid complexes: Manufacturing highly moldable 3D aerated foods - Yujie Lin; Haoyuan Geng; Zengwang Guo; Zhongjiang Wang; Qingfeng Ban; Ningzhe Wang (Food Hydrocolloids, 2025)

The effect of vessel noise on behavior and physiology of orange-spotted grouper (Epinephelus coioides) under conditions with and without artificial lighting - Hui Liu; Zijian Lu; Pingping Shen; Kaicheng Zhang; Geng Qin; Jianping Yin; Qiang Lin; Huixian Zhang (Marine Pollution Bulletin, 2025)

Projected impacts of ocean warming on pelagic ecosystems in the Western and Central Pacific Ocean using a multi-species size-spectrum model - Xiaodong Li; Zhe Geng; Qinqin Lin; Richard Kindong; Yang Wang; Jiangfeng Zhu (Marine Pollution Bulletin, 2025)

Concentrated mannan oligosaccharide supports grass carp (Ctenopharyngodon idellus) health during Ichthyophthirius multifiliis infection: Histopathological and immunological study - Fulong Li; Ming Xu; Baipeng Chen; Senyue Liu; Yanhao Cao; Yufan Zhang; Gang Lin; Ping Ouyang; Defang Chen; Yi Geng; Xiaoli Huang (Aquaculture, 2025)

Core function and mechanism of electrospun carbon nanofiber aerogels/CNTs for accelerating electron transfer efficiency in microbial fuel cell - Xiaoqiu Lin; Zijing Su; Yuanhao Geng; Ling Wang; Zhiling Li; Haoxu Liu; Congju Li (Journal of Environmental Chemical Engineering, 2025)

Bioreduction-assisted synthesis of Co nanoclusters for selective singlet oxygen generation in ciprofloxacin degradation - Yuning Fan; Wenqian Zhang; Yaping Geng; Jiangjun Lin; Yefei Su; Kai Teng; Jiajie wu; Qing Qu; Lei Li (Journal of Environmental Chemical Engineering, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

Origin-dependent quality traits of Stropharia rugosoannulata: A comprehensive analysis of nutritional, aroma, and taste biomarkers - Yue Geng; Songyi Lin; Ruixue Wang; Liren Zhao; Shuo Xu; Dong Chen (Food Bioscience, 2025)

Reversal of neurodevelopmental toxicity induced by combined exposure to the neonicotinoid insecticides acetamiprid and imidacloprid in zebrafish through targeting DRP-1: insights into mitophagy and apoptosis mechanisms - Yuzhi Zhao; Shaozhuo Wang; Siyue Tan; Gaoyuan Wang; Haojie Zhou; Chengyu Geng; Chunjin Li; Yuewen He; Yifan Shi; Zhongxiu Deng; Siyu Chen; Qitong Yuan; et al. (Environmental Pollution, 2025)

In Vitro and Animal Studies of Human Natural Killer Cell-Derived Exosomes for the Treatment of Otitis Media - Zirui Zhao; Liqin Wang; Zhen Guo; Kanglun Jiang; Jianghong Xu; Yilai Shu; Christina Y. Xu; Jianning Zhang; Yunfeng Wang; Geng-Lin Li (Neuroscience Bulletin, 2025)

High-frequency sequence patterns in lacustrine basins: Insights from delta-hyperpycnal flow systems in the Middle Jurassic shale interval, Sichuan Basin, China - Haocheng Shi; Benzhong Xian; Yichen Liu; Zhiyun Yu; Lin Zhao; Junyang Geng; Rongheng Tian; Qianran Wu; Li Liu; Yujie Shuai; Yi Shu (Sedimentary Geology, 2025)

A grid search-based optimal trajectory planning approach for automatic berthing of underactuated unmanned surface vehicles - Shidi Wu; Shifeng Ding; Lin Geng; Zihan Chen; Sen Han; Li Zhou (Ocean Engineering, 2025)

H3K18 lactylation drives the progression of silica nanoparticles-induced pulmonary fibrosis via promoting macrophage M1 polarization - Lili Shi; Lin Zhang; Zhenfang Ma; Zhaohui Hu; Zihan Geng; Hao Liu; Jingyuan Wang; Ke Feng; Yiheng Geng; Yan Liu; Cunhui Zhang; Yujia Xie; et al. (Journal of Hazardous Materials, 2025)

Interaction mechanisms of sea cucumber proteins with flavor compounds: Adsorption behavior, dynamic equilibrium and structural changes - Xinran Li; Jiahui Song; Jian Jiao; Qiang Geng; Songyi Lin (Food Chemistry, 2025)

Lipid molecule profiling in Lentinula edodes during hot air drying via untargeted lipidomics: Composition, dynamic variations and contribution to characteristic flavor - Ruixue Wang; Songyi Lin; Lei Qin; Silu Wang; Yue Geng; Dong Chen (Food Bioscience, 2025)

Impacts on structure, lipase-inhibitory activity, and digestive characters of fermented coconut protein with Lactobacillus strains - Yufang Tian; Tao Lin; Kai Ma; Changliang Zhang; Feng Ji; Shuo Geng; Elham Azarpazhooh; Marjan Ajami; Ghahvechi Chaeipeima Masha; Xin Rui; Wei Li (Food Bioscience, 2025)

Growth resilience of juniper shrubs is higher after wet than after dry spells under contrasting climatic conditions - Xiaoming Lu; Zhuosong Geng; Ziying Zhu; Eryuan Liang; Wentao Lin; Jayram Pandey; Shalik Ram Sigdel; Martín A. Hadad; Antonio Gazol; J. Julio Camarero (Regional Environmental Change, 2025)

Discovery of 7-azaindole-3-acrylamide inhibitors of inflammasomes/IL-1β for the treatment of inflammatory bowel disease - Yuyun Yan; Xiuxiu Zhang; Ruiwen Wu; Xiangting Liang; Yiming Luo; Jie Yang; Dan Wu; Geng Lin; Ping Sun; Zhongjin Yang; Wenhui Hu (Molecular Diversity, 2025)

Nutrient limitations drive microbial carbon use efficiency and soil carbon sequestration in grassland restoration - Meiqun Sheng; Muhammad Ibrar; Yanbao Lei; Jie Shen; Xianzhi Deng; Juan Xue; Lin Liu; Geng Sun (Plant and Soil, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Study on the correlation between Flavobacterium columnare infection and gill injury in Largemouth bass (Micropterus salmoides) and the protective effect of Enoxolone - Chen Li; Yunshan Qiu; Lin Luo; Xinnan Zhou; Hongli Liu; Ping Ouyang; Yi Geng; Defang Chen; Xiaoli Huang (Fish & Shellfish Immunology, 2025)

Laminaria Japonica hydrolysate as a novel biostimulant for enhancing DHA accumulation in Aurantiochytrium limacinum - Jia-Xue Lin; Ying Wang; Shao-Geng Zhao; Bei-Chen Huang; Yue Zhang; Zhi-Qiang Wang; Sheng-Jie Li; Qian Liu; Yan Ma; Jing-Run Ye; Hai-Ying Wang; Zhi-Peng Wang (World Journal of Microbiology and Biotechnology, 2025)

Habitat‐Forming Species: Buffers or Amplifiers for Mutualistic Organisms in Response to Climate Change? - Junmei Qu; Zhixin Zhang; Shaobo Ma; Yaqi Wang; Xiaoyu Tang; Jianping Yin; Geng Qin; Qiang Lin (Journal of Biogeography, 2025)
Aim Habitat‐forming species play a critical role in coral reef ecosystems by creating complex physical structures for marine species. Driven by climate change, these habitat‐forming species are undergoing considerable shifts in their geographical distribution, which might trigger cascading effects via protection mutualisms, leading to alterations in the relationships between species. We examined the role of habitat‐forming species in regulating spatial distributions of their mutualistic protectors' influence. Location Global coastal ocean. Methods We used species distribution models to examine how suitable habitats for organisms that form mutualistic relationships with habitat‐forming species respond to climate change, focusing on two representative macrosymbiotic relationships in coral reefs: Coral–coral crab and sea anemone–clownfish. Results The results revealed that corals are more sensitive to climate change than sea anemones, experiencing greater range contractions under projected future conditions. Consequently, the distribution ranges of both coral‐mutualistic crabs and sea anemone‐mutualistic clownfishes are expected to reduce even further when protection mutualisms are considered. Coral crabs are projected to undergo a more rapid range size loss than clownfishes. Main Conclusion These findings highlight the importance of incorporating interspecific interactions among habitat‐forming species into predictions of potential shifts in the biogeographic distributions of mutualistic protectors under climate change.

Differences in predictions of marine species distribution models based on expert maps and opportunistic occurrences - Zhixin Zhang; Jamie M. Kass; Ákos Bede‐Fazekas; Stefano Mammola; Junmei Qu; Jorge García Molinos; Jiqi Gu; Hongwei Huang; Meng Qu; Ying Yue; Geng Qin; Qiang Lin (Conservation Biology, 2025)
Species distribution models (SDMs) are important tools for assessing biodiversity change. These models require high‐quality occurrence data, which are not always available. Therefore, it is increasingly important to determine how data choice affects predictions of species’ ranges. Opportunistic occurrence records and expert maps are both widely used sources of species data for SDMs. However, it is unclear how SDMs based on these data differ in performance, particularly for the marine realm. We built SDMs for 233 marine fish species from 2 families with these 2 occurrence data types and compared their performances and potential distribution predictions. Opportunistic occurrences were sourced from field surveys in the South China Sea and online repositories and expert maps from the International Union for Conservation of Nature Red List database. We used generalized linear models to explore drivers of differences in prediction between the 2 model types. When projecting to distinct regions with no occurrence data, models calibrated using opportunistic occurrences performed better than those using expert maps, indicating better transferability to new environments. Differences in marine predictor values between the 2 data types accounted for the dissimilarity in model predictions, likely because expert maps included large areas with unsuitable environmental conditions. Dissimilarity levels among fish families differed, suggesting a taxonomic bias in biodiversity data between data sources. Our findings highlight the sensitivity of species distribution predictions to the choice of distributional data. Although expert maps have an important role in biodiversity modeling, we suggest researchers assess the accuracy of these maps and reduce commission errors based on knowledge of target species.

Improving in-situ spectral estimation of wetland soil organic carbon by integrating multiple optimization strategies - Hongyi Li; Jiangtao Yang; Bifeng Hu; Yibo Geng; Qian Zhu; Yongsheng Hong; Yi Lin; Jie Peng; Wenjun Ji; Songchao Chen; Zhou Shi (CATENA, 2025)

Exploring exhaled volatile organic compounds as potential biomarkers in anti-MDA5 antibody-positive interstitial lung disease - Yuxuan Wang; Xuewen Wang; Luqin Yang; Ke Wang; Fengqin Zhang; Huihui Yue; Junqi Wang; Minhua Peng; Pengnan Fan; Xiangcheng Qiu; Han Zhang; Wei Lin; et al. (Molecular and Cellular Biochemistry, 2025)

Safranal ameliorates atherosclerosis progression partly via repressing PI3K/Akt and NF-κB signaling pathways in ApoE (−/−) mice - Yining Geng; Manping Song; Bing Huang; Ru Lin; Shiwen Wu; An Lin (Journal of Natural Medicines, 2025)

Forest or grassland? A quantitative analysis of urban residents' green exposure preference by using multi-temporal mobile signal data - Hongkai Geng; Tao Lin; P.M. van Bodegom; Mingming Hu; Yicheng Zheng; Zixu Jia; Junmao Zhang; Xiangzhong Guo; Yuan Chen; Meixia Lin; Jiayu Cai; Jing Lin (Urban Forestry & Urban Greening, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

The modulatory effects of shiitake mushrooms on the quality and flavor profiles of steamed low-salt chicken meatballs - Yue Geng; Songyi Lin; Hongli Wang; Yantong Li; Menglong Sheng; Dong Chen (International Journal of Gastronomy and Food Science, 2025)

Hierarchical carbon cloth with Co-N nanoneedle arrays: enabling highly reversible lithium metal anode via enhanced lithiophilicity and structural confinement - Jinping Xu; Meina Huang; Cheng Zhang; Zhen Wang; Xin Xiao; Peiwan Guo; Qianyu Fan; Shize Geng; Xin Lin; Lizhe Liang; Dechao Wang; Taiyu Lyu; et al. (Chemical Engineering Journal, 2025)

The longitudinal loading mode evaluation of fault-crossing tunnel by a new load equivalence method based on a Pasternak model - Tianqiang Wang; Ping Geng; Chenyang Xiang; Guoguo Liu; Qi Wang; Lin Deng; Shiqiang Ma (Bulletin of Engineering Geology and the Environment, 2025)

Dietary spermine supplementation enhances growth, protein synthesis, and antioxidant capacity in hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Lina Geng; Chirun Lin; Guojian Pan; Yusen Yang; Lixing Wang; Shengming Huang; Zhiyu Zhou; Haoran Yin; Xiaoyi Wu (Aquaculture, 2025)

Quantitative threshold effects identification of urban green exposure on multidimensional human health – A case study in Xiamen City, China - Yicheng Zheng; Nicholas A.S. Hamm; Tao Lin; Jue Liu; Tongyu Zhou; Xiaopeng Ren; Xinwen Bai; Hongkai Geng; Junmao Zhang; Zixu Jia; Yuan Chen (Urban Forestry & Urban Greening, 2025)

Urbanization-induced vegetation phenological changes: Variability across vegetation types and zones in China - Yuan Chen; Tao Lin; Yicheng Zheng; Junmao Zhang; Zixu Jia; Hongkai Geng; Meixia Lin; Xia Yao; Yuqin Liu (Urban Forestry & Urban Greening, 2025)

Revealing the driving mechanism of soil respiration induced by water erosion in Ultisols landscape of southern China - Geng Guo; Zhiying Deng; Jie Kuai; Xiaoying Peng; Lihua Wu; Guangruo Zeng; Zhen Ouyang; Jiayi Miao; Jie Lin (Soil and Tillage Research, 2025)

Corrigendum to “Redistribution of vocal snapping shrimps under climate change” [Sci. Total. Environ. 954 (2024) 176191] - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2025)

Debromination of decabromodiphenyl ether (BDE-209) and bacterial community responses in aerobic and anaerobic soil microcosms - Shasha Fang; Yue Geng; Lu Wang; Jun Zeng; Xiangui Lin; Shimin Zhang; Yucheng Wu (Journal of Hazardous Materials, 2025)

Enhancing occupant-centric ventilation control in airport terminals: A predictive optimization framework integrating agent-based simulation - Hao Tang; Juan Yu; Yang Geng; Xue Liu; Zujian Huang; Yuren Yang; Zhe Wang; Ying Chen; Borong Lin (Building and Environment, 2025)

Aligning GPS/Galileo/BDS satellite integer clock products across day boundaries for continuous time and frequency transfer - Jihang Lin; Jianghui Geng; Qiyuan Zhang (Journal of Geodesy, 2025)

Genotyping and antimicrobial susceptibility of Aeromonas veronii isolated from aquatic animals in Sichuan, China - Kun Peng; Silu Tian; Longjun Deng; Yu Yuan; Zixuan Cheng; Tiancai Li; Keyu Zhou; Jingyi Lin; Yi Geng (Antonie van Leeuwenhoek, 2025)

Mitigation pathways of urban heat islands and simulation of their effectiveness from a perspective of connectivity - Qiuyue Zhao; Ling Tao; Hanyue Song; Yuhang Lin; Yuejiao Ji; Jianwei Geng; Kunyong Yu; Jian Liu (Sustainable Cities and Society, 2025)

Tight origin and hydrocarbon potential of shell interlayers in shale: A case of Lower Jurassic Dongyuemiao member, Sichuan Basin, China - Zhiyun Yu; Benzhong Xian; Zhenkui Jin; Qianran Wu; Yi Shu; Haocheng Shi; Junyang Geng; Lin Zhao; Yichen Liu (Marine and Petroleum Geology, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Impact of humidity variations at different distances from the lake surface on rhizosphere microbiota of Trifolium repens L - Jin Chen; Meiling Ping; Xiaowan Geng; Keqing Lin; Boyan Wang; Yuxin Zhai; Yizhen Meng; Xiaoyu Li (Physiological and Molecular Plant Pathology, 2025)

Unveiling airborne threats: Vertical profiles of multiple emerging pollutants in PM2.5 across the urban atmosphere of Southern China - Shu-Qing Qiu; Yan-Jun Tang; Li-Xin Hu; Cheng-Lei Pei; Da-Chi Hong; Da-Ying Lin; Geng Kang; Sheng-Zhen Zhou; Bao-Ling Liang; She-Jun Chen; Hong Bai; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Mechanical properties and microstructure of fly ash and slag-based geopolymer prepared by silica fume-based activator - Minguo Lin; Geng Chen; Yonghui Chen; Dandan Han; Ruobin Su; Jing Wu (Journal of Cleaner Production, 2025)

Soil available phosphorus and pH regulate the distribution of Juniperus przewalskii forest understory plant community diversity along an elevation gradient - Zhenjie Dong; Qinghong Geng; Kun Wei; Lin Hou (Forest Ecology and Management, 2025)

ETV5-Mediated Transcriptional Repression of DDIT4 Blocks Macrophage Pro-Inflammatory Activation in Diabetic Atherosclerosis - Lili Shi; Tingting Sun; Di Huo; Lin Geng; Chao Zhao; Wenbo Xia (Cardiovascular Toxicology, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

New insights into transcriptional and metabolic differences between pregnant males and embryos in seahorses - Chunyan Li; Geng Qin; Zelin Chen; Shaobo Ma; Chao Zhang; Qiang Lin (Aquaculture, 2025)

Urbanization induced Urban Canopy Parameters enhance the heatwave intensity: A case study of Beijing - Tuo Chen; Shirao Liu; Xuecao Li; Lin Pei; Mengqing Geng; Guojiang Yu; Zitong Shi; Tengyun Hu (Sustainable Cities and Society, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Online SFE-SFC-MS/MS analysis of pyraclostrobin and chiral mefentrifluconazole residues in mango and mango juice - Hao Yang; Yue Geng; Shu Lin; Lu Wang; Yi Peng; Yaping Xu; Wei Jing; Jing Wei; Zeying He; Xiaowei Liu (Food Chemistry, 2025)

Facile modification of sepiolite and its application in wear-resistant and superhydrophobic epoxy coatings by mimicking the structure of shark skin - Na Sun; Zhanfeng Hou; Zeshang Jiang; Jieting Geng; Lin Xia (Applied Clay Science, 2025)

Better objective sleep quality is associated with higher gut microbiota richness in older adults - Maria Teresa Wijaya; Ji-Tseng Fang; Geng-Hao Liu; Yuan-Ming Yeh; Ning-Hung Chen; Chih-Ming Lin; Kuain-Yi Wu; Chih-Mao Huang; Shwu-Hua Lee; Tatia M. C. Lee (GeroScience, 2025)
Aging is associated with disrupted sleep patterns, such as fragmented sleep and reduced efficiency, leading to negative health outcomes. There is evidence of a bidirectional relationship between sleep and gut microbiota, which plays a key role in the gut-brain axis and overall health. However, studies on this relationship in older adults have limited generalizability and show conflicting results, highlighting the need for further research. This study aimed to investigate the associations between sleep quality and gut microbiota composition in healthy Chinese older adults using subjective and objective sleep measures to capture various aspects of sleep quality and explore potential impacts on emotional well-being and cognitive performance. Subjective sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) questionnaire, while objective sleep quality was measured with actigraphy. Gut microbiota sequencing was performed on stool samples. The results show a robust positive association between gut microbiota richness and objective sleep quality in older adults, independent of subjective sleep quality and demographics, lifestyle, and health covariates. However, no significant link was found between gut microbiota richness and subjective sleep quality. Specific taxa like Bacteroidetes, Ruminococcus , Collinsella , Veillonella , and Holdemania were tentatively linked to sleep quality. These findings emphasize the connection between sleep quality and gut microbiota composition in older adults with potential research and clinical implications, improving our understanding of the mechanisms underlying the sleep-gut microbiota relationship and guiding the development of interventions for improving both sleep quality and gut health in older adults.

Effects of Oxygen Enrichment and Air Humidification on the Combustion and Emissions of the Biodiesel Marine Diesel Engine - Peng Geng; Xiong Hu; Xiaohu Lin (Journal of Marine Science and Engineering, 2025)
With increasingly strict emission regulations, research on diesel engine combustion and emissions is urgently needed. This study conducted computational fluid dynamics modeling on diesel engines. The effects of intake humidity and oxygen concentration of a diesel engine on the combustion emission of biodiesel were studied. The results indicate that when the humidity ratio is below 0.4 (WR = 0.4), intake humidification has a certain promoting effect on the combustion reaction process. Water molecule pyrolysis can promote the pyrolysis of biodiesel, and the peak pressure in the cylinder slightly increases. As the intake humidification ratio increases, the cylinder temperature decreases, and the oxygen concentration also decreases due to the increase in water molecular weight. The combustion reaction process is suppressed, and the cylinder pressure decreases. When the humidity ratio is 1 (WR = 1), the peak pressure decreases by 2.61% compared to when it is not humidified (WR = 0). The concentration of O radicals decreases with an increase in humidity ratio. When WR = 1.0, the emissions of NOx decreased by 55.02%, but with the decrease in oxygen concentration in the high-temperature area, the emissions of soot increased. The results indicate that as the oxygen concentration increases, the cylinder pressure and average temperature increase, the ignition-delay time decreases, the heat-release rate increases, and it ultimately leads to an increase in NOx emissions.

The potential role of galectin-4 in protecting the intestinal barrier in the lined seahorse Hippocampus erectus - Wei Huang; Jinhui Sun; Geng Qin; Zhixin Zhang; Yongli Wu; Yuan Zhang; Ying Liu; Zixuan Liu; Qiang Lin; Wanghong Xiao (Aquaculture, 2025)

Optimizing organic pollutant removal from hydrazine hydrate waste brine through thermal activation of sodium persulfate assisted by response surface methodology - He Sun; Guohao Geng; Shilong Lin; Doufeng Wu; Sanchuan Yu; Congjie Gao (Journal of Water Process Engineering, 2025)

An assessment of the levels of emerging and traditional organophosphate ester flame retardants in dairy products in China and their combined dietary risks - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Baolong Wang; Yantao Wu; Wei Li (Food and Chemical Toxicology, 2025)

Judicious inhibition of interfacial non-radiative recombination via chlorine-isomerized self-assembled molecules for efficient and durable organic solar cells - Hao Xu; Xingting Liu; Shanlei Xu; Kin-Long Wong; Xinjie Zhou; Huilong Chen; Yijin Lin; Renyong Geng; Weiguo Zhu; Jun Yin; Xin Song (Chemical Engineering Journal, 2025)

Distinct co-occurrence patterns and assembly processes of abundant and rare taxa under cadmium stress in volcanic areas - Qingchen Xiao; Boyan Wang; Ye Cui; Zishan Li; Xiaowan Geng; Keqing Lin; Xiaoyu Li; Jin Chen (CATENA, 2025)

Evaluating the impacts of converting grain to vegetable fields on nitrate transport in the deep vadose zone of the North China Plain - Meiying Liu; Leilei Min; Lin Wu; Yucui Zhang; Yongqing Qi; Shiqin Wang; Binbin Liu; Di Geng; Yanjun Shen (Journal of Geographical Sciences, 2025)

Cement and zeolite stabilization/solidification of heavy metal-contaminated sediments: 841-Day leaching characteristics, mechanisms, and microstructure - Nan Hu; Geng Chen; Yonghui Chen; Minguo Lin; Panpan Tang; Wanlu Zhang; Zi Ye (Waste Management, 2024)

Fecal microbiota transplantation as an effective way in treating methylmercury-poisoned rats - Yanfei Zhang; Qingxuan Liu; Hongxin Xie; Wei Zhang; Xiaoying Lin; Huifeng Zhang; Huan Yu; Yinghui Ma; Chuang Zhang; Hao Geng; Nianqiu Shi; Liwei Cui; et al. (Science of The Total Environment, 2024)

Redistribution of vocal snapping shrimps under climate change - Junmei Qu; Geng Qin; Hongwei Huang; Shaobo Ma; Qiang Lin; Zhixin Zhang; Jianping Yin (Science of The Total Environment, 2024)

Unraveling the effects of prenatal anesthesia on neurodevelopment: A review of current evidence and future directions - Qiu-Xia Xiao; Min-Jian Geng; Qiu-Lin Wang; Chang-Le Fang; Jing-Han Zhang; Qi Liu; Liu-Lin Xiong (NeuroToxicology, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

The antibacterial defence role of β-defensin in the seahorse testis - Wei Huang; Wanghong Xiao; Geng Qin; Zijian Lu; Xiaoqian Peng; Ying Liu; Qiang Lin; Jinhui Sun (Fish & Shellfish Immunology, 2024)

Characterization of microbial structure and function in the rhizosphere of Boehmeria nivea L.: A comparative study of volcanic cone and crater - Jin Chen; Yiming Zhang; Qingchen Xiao; Boyan Wang; Zishan Li; Keqing Lin; Xiaowan Geng; Xiaoyu Li (Soil Ecology Letters, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Direct recovery of high-purity lithium via nanofiltration membranes from leaching solution of spent lithium batteries - Shiweihua He; Qiuyang Zuo; Hui Shi; Zhiwei Geng; Congcong Liu; Lin Ding; Xin Li; Penghui Shao; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2024)

Vegetation greening mitigates the positive impacts of climate change on water availability in Northwest China - Zixu Jia; Tao Lin; Xiangzhong Guo; Yicheng Zheng; Hongkai Geng; Junmao Zhang; Yuan Chen; Wenhui Liu; Meixia Lin (Journal of Hydrology, 2024)

Urban green vitalization and its impact on green exposure equity: A case study of Shanghai city, China - Hongkai Geng; Tao Lin; Ji Han; Yicheng Zheng; Junmao Zhang; Zixu Jia; Yuan Chen; Meixia Lin; Long Yu; Yukui Zhang (Journal of Environmental Management, 2024)

Effect of plant species on wastewater treatment performance of a subsurface vertical-flow constructed wetland with step-feeding at low temperature - Menglu Huang; Lin Zhao; Zhen Wang; Ximing Sun; Qiongqiong Shang; Yihan Li; Mengxiao Li; Hongzhi Geng; Siyu Hu; Yongkui Yang (Journal of Environmental Management, 2024)

Multi-omics integration analysis: Tools and applications in environmental toxicology - Chengcheng Shi; Lin Cheng; Ying Yu; Shuangshuang Chen; Yubing Dai; Jiajia Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Environmental Pollution, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

MXene-based nanozymes remodel tumor microenvironment for heterojunction-enhanced sonodynamic and chemodynamic therapy to boost robust cancer immunotherapy - Lin Zhao; Jin Ji; Nan Wang; Chen Kong; Yinhui Yang; Xin Lu; Bijiang Geng; Shengfei Qin; Xiang Feng; Zhi Cao (Chemical Engineering Journal, 2024)

Study on Preclinical Safety and Toxic Mechanism of Human Umbilical Cord Mesenchymal Stem Cells in F344RG Rats - Xiaofang Hao; Hao Zhu; Chao Qin; Lulu Li; Zhi Lin; Hua Jiang; Qianqian Li; Yan Huo; Hezhan Zhang; Xingchao Geng; Ying Huang; Bo Li (Stem Cell Reviews and Reports, 2024)

Allicin Ameliorated High-glucose Peritoneal Dialysis Solution-induced Peritoneal Fibrosis in Rats via the JAK2/STAT3 Signaling Pathway - Linwang Gan; Lei Geng; Qiancheng Li; Liling Zhang; Yan Huang; Jiaru Lin; Santao Ou (Cell Biochemistry and Biophysics, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

Unraveling microbial community variation along a salinity gradient and indicative significance to groundwater salinization in the coastal aquifer - Chuanshun Zhi; Xiaonong Hu; Fan Yang; Xianrui Huang; Hongfan Chen; Lin Chen; Geng Chen; Zhen Wu; Shuqiang Wang (Journal of Hydrology, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

The perfluoroalkylthiolation reaction of thiols with perfluoroalkanesulfenic acids - Ye-lin Liu; Xiao-Yu Geng; Min Jiang; Jin-Tao Liu (Journal of Fluorine Chemistry, 2024)

Distinct species turnover patterns shaped the richness of antibiotic resistance genes on eight different microplastic polymers - Weihong Zhang; Jun Geng; Mengge Sun; Chunxia Jiang; Hui Lin; Haiyang Chen; Yuyi Yang (Environmental Research, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

WNT2B high‑expressed fibroblasts induce the fibrosis of IBD by promoting NK cells secreting IL-33 - Yanling Cheng; Shuzhe Xiao; Lin Lan; Danqiong Liu; Rui Tang; Jianbiao Gu; Li Ma; Zhihua He; Xirong Chen; Lanlan Geng; Peiyu Chen; Huiwen Li; et al. (Journal of Molecular Medicine, 2024)

Pollution Characteristics and Risk Assessment of Heavy Metals in Dujiangyan Irrigation District, China - Yang Qiao; Hongling Yin; Shuyu Lin; Xiaoke Guo; Hui Zhang; Geng Ge; Yuxiang Lu (International Journal of Environmental Research, 2024)

Spatiotemporal Evolution of Urban Heat Islands and Optimization of Spatial Network Construction in the Central Urban Area of Fuzhou City, China - Qiuyue Zhao; Kunyong Yu; Jianwei Geng; Jiqing Lin; Jingwen Ai; Jian Liu (Chinese Geographical Science, 2024)

Characterization of the novel bequatrovirus vB-BcgM and its antibacterial effects in food matrices - Yunfei Gong; Lin Sun; Xiaofu Wan; Peiling Geng; Xiaomin Hu (Archives of Virology, 2024)

Insights gained into the injury mechanism of drug and herb induced liver injury in the hepatic microenvironment - Xiaomeng Zhang; Qi Geng; Lin Lin; Lulu Zhang; Changqi Shi; Bin Liu; Lan Yan; Zhiwen Cao; Li Li; Peipei Lu; Yong Tan; Xiaojuan He; et al. (Toxicology, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Dual-carbon isotope analysis of benzene polycarboxylic acids for tracking black carbon across different environments - Xin Yi; Guangcai Zhong; Xiaofei Geng; Jiao Tang; Boji Lin; Sanyuan Zhu; Shutao Gao; Chuxin Yao; Zhineng Cheng; Shizhen Zhao; Jun Li; Gan Zhang (Applied Geochemistry, 2024)

A hybrid deep learning framework for predicting industrial wastewater influent quality based on graph optimisation - Jiafei Cao; Anke Xue; Yong Yang; Rongfeng Lu; Xiaojing Hu; Le Zhang; Wei Cao; Guanglong Cao; Xiulin Geng; Lin Wang (Journal of Water Process Engineering, 2024)

Soil organic matter components and sesquioxides integrally regulate aggregate stability and size distribution under erosion and deposition conditions in southern China - Geng Guo; Yu Kong; Yanyin Xu; Xiaoying Peng; Manting Niu; Guangruo Zeng; Zhen Ouyang; Jun Liu; Chen Zhang; Jie Lin (Journal of Hydrology, 2024)

Contamination of dairy products with tris(2,4-di-tert-butylphenyl) phosphite and implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Tongna Mu; Baolong Wang; Ting Liu (Food Chemistry, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Morphological convergence from independent crab lineages contributes to the flourishing symbiotic diversity between crabs and branching corals - Shaobo Ma; Zelin Chen; Yuli Sun; Meng Qu; Xin Wang; Wei Jiang; Geng Qin; Qiang Lin (Coral Reefs, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Spatiotemporal dynamic mapping of heat exposure risk for different populations in city based on hourly multi-source data - Junmao Zhang; Xia Yao; Yuan Chen; Meixia Lin; Tao Lin; Yunkai Zheng; Hongkai Geng; Yicheng Zheng; Xian Wu; Guoqing Zhang; Hong Ye (Sustainable Cities and Society, 2024)

A 76-m per pixel global color image dataset and map of Mars by Tianwen-1 - Jianjun Liu; Xin Ren; Wei Yan; Wangli Chen; Xingguo Zeng; Xiaoxia Zhang; Xu Tan; Xingye Gao; Qiang Fu; Dingxin Liu; Lin Guo; Qing Zhang; et al. (Science Bulletin, 2024)

Rationally engineered core-shell structured Fe0@FeS towards the efficacious synergistic Cr(VI) and Ni(II) removal - Zishen Lin; Chunli Zheng; Zhenxing Wang; Yuanzhe Peng; Guoqing Geng; Aibin Zhu; Chi He (Chemical Engineering Journal, 2024)

Ultrasmall copper-based nanoplatforms for NIR-II light-triggered photothermal/ photodynamic and amplified nanozyme catalytic therapy of hypoxic tumor - Mengshu Xu; Ruoxi Zhao; Bin Liu; Fang Geng; Xiaodan Wu; Feng Zhang; Ruifang Shen; Huiming Lin; Lili Feng; Piaoping Yang (Chemical Engineering Journal, 2024)

Growth increase and gonadal dysfunction of the lined seahorse triggered by zinc exposure - Xue Han; Chunyan Li; Geng Qin; Xin Wang; Bo Zhang; Qiang Lin (Aquatic Toxicology, 2024)

Stem Cell Therapy in Neonatal Hypoxic-Ischemic Encephalopathy and Cerebral Palsy: a Bibliometric Analysis and New Strategy - Qiu-Xia Xiao; Min-Jian Geng; Yi-Fei Sun; Yu Pi; Liu-Lin Xiong (Molecular Neurobiology, 2024)

Different microbial functional traits drive bulk and rhizosphere soil phosphorus mobilization in an alpine meadow after nitrogen input - Bing Han; Yicheng He; Ji Chen; Yufei Wang; Lina Shi; Zhenrong Lin; Lu Yu; Xiaoting Wei; Wantong Zhang; Yiyi Geng; Xinqing Shao; Shangang Jia (Science of The Total Environment, 2024)

Overexpression of a plasmalemma Na+/H+ antiporter from the halophyte Nitraria sibirica enhances the salt tolerance of transgenic poplar - Shouye Chen; Xin Geng; Jing Lou; Duoman Huang; Huiping Mao; Xiaofei Lin (Plant Science, 2024)

Seasonal predictability of SST anomalies and marine heatwaves over the Kuroshio extension region in the Copernicus C3S models - Chenguang Zhou; Hong-Li Ren; Yu Geng; Run Wang; Lin Wang (Ocean Modelling, 2024)

High-performance ceramic coatings for additive manufacturing biofunctional titanium alloy by regulating precipitation orientation - Yamei Mao; Qinyang Zhao; Jihua Geng; Weifeng Qian; Haiyan Zou; Tao Gong; Yongnan Chen; Guangrui Gao; Lin Wang; Yongqing Zhao (Chemical Engineering Journal, 2024)

Environmental Flow Increases The Riparian Vegetation Diversity And Community Similarity - Min Guo; Wan-Lai Xue; Chen Wang; Wen-Zhong Li; He Gao; Neil Saintilan; Cheng-Lin Li; Geng Huang; Yu-Yu Wang (Wetlands, 2024)

A novel ESIPT fluorescent probe for early detection and assessment of ferroptosis-mediated acute kidney injury via peroxynitrite fluctuation - Miao Chen; Shuiling Lin; Bingbing Tang; Tian Tian; Yahui Leng; Danwen Liu; Kelong Wang; Yi Geng; Zhiguo Luo; Li Shen; Tongsheng Chen (Analytica Chimica Acta, 2024)

Quantitative evaluation of urban green exposure and its impact on human health: A case study on the 3–30-300 green space rule - Yicheng Zheng; Tao Lin; Nicholas A.S. Hamm; Jue Liu; Tongyu Zhou; Hongkai Geng; Junmao Zhang; Hong Ye; Guoqin Zhang; Xiaotong Wang; Tianyi Chen (Science of The Total Environment, 2024)

Metabolic disturbance of short- and medium-chain chlorinated paraffins to zebrafish larva - Shuangshuang Chen; Xiaoqian Ren; Ying Yu; Lin Cheng; Guanghui Ding; Hairong Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Potential roles of hydroxybenzoate paralytic shellfish toxins in modulating toxin biokinetics in scallops - Zhuo-Ru Lin; Hui-Xia Geng; Ren-Cheng Yu (Journal of Hazardous Materials, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

The Mh-miR393a-TIR1 module regulates Alternaria alternata resistance of Malus hupehensis mainly by modulating the auxin signaling - Xinyi Yu; Kaixu Hu; Xiaoyue Geng; Lifang Cao; Tingting Zhou; Xinxin Lin; Hongcheng Liu; Jingrui Chen; Changguo Luo; Shenchun Qu (Plant Science, 2024)

Transesterification of acidic palm oil using solid waste/CaO as a bifunctional catalyst - Jisen Liu; Tong Lin; Shengli Niu; Jie Zhu; Zihao Yang; Jie Geng; Sitong Liu; Yue Zheng; Bo Liang; Xiaobin Sun; Huaji Zhang (Fuel, 2024)

Effects of Lentinus Edodes on the physico-chemical, oxidation and flavor characteristics of carp surimi - Qinglong Kong; Songyi Lin; Menglong Sheng; Yue Geng; Zike Zhang; Dong Chen (Food Bioscience, 2024)

Exploring the relationship between library reading space height and user perception: A physiological and subjective analysis - Mengyan Lin; Wen Lu; Ning Li; Wenying Geng (Building and Environment, 2024)

Considering biotic interactions exacerbates the predicted impacts of climate change on coral‐dwelling species - Zhixin Zhang; Shaobo Ma; Ákos Bede‐Fazekas; Stefano Mammola; Meng Qu; Jinxin Zhou; Ellias Yuming Feng; Geng Qin; Qiang Lin (Journal of Biogeography, 2024)
Aim Climate change is affecting the geographic distributions of many species and researchers are increasingly relying on species distribution models (SDMs) to forecast species' redistributions under climate change. Such modelling studies, however, often ignore biotic interactions that shape species' geographic ranges. This is especially problematic for coral reefs, which host a high diversity of species and interactions. We tested how biotic interactions affect the distribution patterns of obligate coral‐dwelling Trapezia crabs. Location Global coastal ocean. Time Period 2000–2014, 2040–2050, 2090–2100. Major Taxa Studied Corals and coral‐dwelling Trapezia crabs. Methods We determined the symbiotic relationships between 22 crab species in the genus Trapezia and corals via field survey and extensive literature review. We first developed SDMs for coral and crab species using exclusively abiotic variables (abiotic‐only models for corals and crabs). Then we constructed a second set of models where we accounted for coral distributions into crab predictions by combining model predictions for the two taxa a posteriori (abiotic‐plus‐biotic models for crabs only). Results We obtained 30 commonly accepted coral‐crab symbiotic relationships from nine Trapezia crab and six stony coral species. The abiotic‐only model predictions showed that six corals may lose approximately one‐sixth of suitable ranges under RCP 8.5 in 2040–2050. The two types of models for crabs yielded largely different habitat suitability predictions and accounting for biotic interactions into SDM predictions exacerbates the predicted impacts of climate change on coral‐dwelling crabs. Main Conclusions Our results show large discrepancies in crab spatial distribution patterns with and without accounting for symbiotic interactions. Our findings highlight the important role of modeller's decision on accounting for biotic interactions when predicting the geographical ranges of coral‐dwelling species, with important implications for designing future conservation and management strategies for marine species.

Development of a multi-spectroscopy method coupling μ-FTIR and μ-Raman analysis for one-stop detection of microplastics in environmental and biological samples - Zhichun Zhang; Yang Geng; Wei Zhou; Xuehua Shao; Hua Lin; Ying Zhou (Science of The Total Environment, 2024)

Integrated evidence of transcriptional, metabolic, and intestinal microbiota changes in Ruditapes philippinarum due to perfluorooctanoic acid-induced immunotoxicity - Fengling Li; Xiuqiong Gong; Yang Zhou; Qianqian Geng; Yanhua Jiang; Lin Yao; Meng Qu; Zhijun Tan (Science of The Total Environment, 2024)

Coupling between 2, 2′, 4, 4′-tetrabromodiphenyl ether (BDE-47) debromination and methanogenesis in anaerobic soil microcosms - Shasha Fang; Yue Geng; Lu Wang; Jun Zeng; Shimin Zhang; Yucheng Wu; Xiangui Lin (Science of The Total Environment, 2024)

Acidified water promotes silver-induced toxicity in zebrafish embryos - Jiun-Lin Horng; Geng-Xin Kung; Li-Yih Lin (Aquatic Toxicology, 2024)

A New Approach for Exploring Reperfusion Brain Damage in Hypoxic Ischemic Encephalopathy - Tianlei Zhang; Zhiwei Zhang; Jiayi Geng; Kexin Lin; Xinru Lin; Mengdie Jiao; Jianghu Zhu; Xiaoling Guo; Zhenlang Lin (Molecular Neurobiology, 2024)

Long-Term Effects of Ecological Restoration Projects on Ecosystem Services and Their Spatial Interactions: A Case Study of Hainan Tropical Forest Park in China - Jiahui Zhong; Linlin Cui; Zhiyin Deng; Yong Zhang; Jie Lin; Geng Guo; Xiang Zhang (Environmental Management, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Research on the Drift Prediction of Marine Floating Debris: A Case Study of the South China Sea Maritime Drift Experiment - Lin Mu; Haiwen Tu; Xiongfei Geng; Fangli Qiao; Zhihui Chen; Sen Jia; Ruifei Zhu; Tianyu Zhang; Zhi Chen (Journal of Marine Science and Engineering, 2024)
Annually, hundreds of individuals tragically lose their lives at sea due to shipwrecks or aircraft accidents. For search and rescue personnel, the task of locating the debris of a downed aircraft in the vastness of the ocean presents a formidable challenge. A primary task these teams face is determining the search area, which is a critical step in the rescue operation. The movement of aircraft wreckage on the ocean surface is extremely complex, influenced by the combined effects of surface winds, waves, and currents. Establishing an appropriate drift motion prediction model is instrumental in accurately determining the search area for the wreckage. This article initially conducts maritime drift observation experiments on wreckage, and based on the results of these experiments, analyzes the drift characteristics and patterns of the debris. Subsequently, employing a wealth of observational experimental data, three types of drift prediction models for the wreckage are established using the least squares method. These models include the AP98 model, the dynamics model, and an improved model. In conclusion, the effectiveness and accuracy of the three models is evaluated and analyzed using Monte Carlo techniques. The results indicate that the probability of positive crosswind leeway (CWL) is 47.4%, while the probability of negative crosswind leeway (CWL) is 52.6%. The jibing frequency is 7.7% per hour, and the maximum leeway divergence angle observed is 40.4 degrees. Among the three drift prediction models, the refined AP98 drift model demonstrates the highest forecasting precision. The findings of this study offer a more accurate drift prediction model for the search of an aircraft lost at sea. These results hold significant guiding importance for maritime search and rescue operations in the South China Sea.

Chronic ammonia stress caused disorder of intestinal microbiota and damaged intestinal structure and function in yellow catfish (Pelteobagrus fulvidraco) - Lin Luo; Senyue Liu; Baipeng Chen; Fulong Li; Yongqiang Deng; Xiaoli Huang; Yi Geng; Ping Ouyang; Defang Chen (Aquaculture, 2024)

Estimation of annual soil CO2 efflux under the erosion and deposition conditions by measuring and modeling its respiration rate in southern China - Geng Guo; Xiao Li; Jie Kuai; Xiang Zhang; Xiaoying Peng; Yanyin Xu; Guangruo Zeng; Jun Liu; Chen Zhang; Jie Lin (Journal of Environmental Management, 2024)

Understanding Urban Vitality from the Economic and Human Activities Perspective: A Case Study of Chongqing, China - Fiona Fan Yang; Geng Lin; Yubing Lei; Ying Wang; Zheng Yi (Chinese Geographical Science, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Bibliometric analysis and systematic review of the adherence, uptake, translocation, and reduction of micro/nanoplastics in terrestrial plants - Yang Li; Lin Zhao; Yi An; Li Qin; Zhi Qiao; Daying Chen; Yihan Li; Hongzhi Geng; Yongkui Yang (Science of The Total Environment, 2024)

Effects of combined polystyrene nanoplastics and ibuprofen on the activated sludge processes: Short-term exposure in pure cultures versus long-term stress in mixed communities - Daying Chen; Mengxiao Li; Yang Li; Sha Long; Ximing Sun; Hongzhi Geng; Meilin Yin; Yongkui Yang; Lin Zhao (Journal of Water Process Engineering, 2024)

Screening and degradation characteristics of plastic-degrading microorganisms in film-mulched vegetable soil - Zhenyan Lin; Tuo Jin; Xin Xu; Xiao Yin; Dan Zhang; Mengjiao Geng; Chunyu Pang; Gongwen Luo; Lizhi Xiong; Jianwei Peng; Jiangchi Fei (International Biodeterioration & Biodegradation, 2024)

Fluid seepage mechanism and permeability prediction model of multi-seam interbed coal measures - Geng Li; Yong Qin; Boyang Wang; Miao Zhang; Yabing Lin; Xuejuan Song; Wentian Mi (Fuel, 2024)

The potential mechanism of concentrated mannan-oligosaccharide promoting goldfish’s (Carassius auratus Linnaeus) resistance to Ichthyophthirius multifiliis invasion - Senyue Liu; Ming Xu; Baipeng Chen; Fulong Li; Yongqiang Deng; Yufan Zhang; Gang Lin; Defang Chen; Yi Geng; Yangping Ou; Xiaoli Huang (Fish & Shellfish Immunology, 2024)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Design strategies for renovation of public space in Beijing's traditional communities based on measured microclimate and thermal comfort - Ning Li; Zhao Guo; Wenying Geng; Lin Li; Ziwei Li (Sustainable Cities and Society, 2023)

Integration approach of transcriptomics and metabolomics reveals the toxicity of Anthracene and its chlorinated derivatives on human hepatic cells - Yun Luo; Ningbo Geng; Shuai Sun; Lin Cheng; Shuangshuang Chen; Haijun Zhang; Jiping Chen (Science of The Total Environment, 2023)

Vacuolar H+-ATPase and BZR1 form a feedback loop to regulate the homeostasis of BR signaling in Arabidopsis - Yu-Tong Jiang; Lu-Han Yang; Ji-Xuan Zheng; Xian-Chen Geng; Yu-Xuan Bai; Yu-Chen Wang; Hong-Wei Xue; Wen-Hui Lin (Molecular Plant, 2023)

Fabrication of a novel gas diffusion electrode (g-C3N4/CB/PTFE-GF) for electro-Fenton treatment of amaranth dye - Daying Chen; Hongzhi Geng; Pengfei Hou; Yihan Li; Sha Long; Meilin Yin; Xiaohui Wang; Lin Zhao (Journal of Water Process Engineering, 2023)

Association of selenium profile with neutralizing antibody response to inactivated SARS-CoV-2 vaccination - Sikang Gao; Na Ren; Taoping Sun; Qi Nie; Sitian Liu; Xuyang Geng; Yao Deng; Zefang Lin; Yu Liu; Li Zhou (Journal of Trace Elements in Medicine and Biology, 2023)

Molten salt-assisted carbonized zeolite imidazolate framework on nickel foam for highly efficient iodide capture in fluoride molten salts - Ming Cheng; Junxia Geng; Yujiao Wang; Qin Lin; Xiaoyu Zhang; Lixin Sun; Qiang Dou; Haiying Fu (Chemical Engineering Journal, 2023)

Relationship between night shift and sleep problems, risk of metabolic abnormalities of nurses: a 2 years follow-up retrospective analysis in the National Nurse Health Study (NNHS) - Heli Zhang; Jingpin Wang; Siwei Zhang; Sumei Tong; Jinping Hu; Ying Che; Lin Zhuo; Peng Wang; Rongmei Geng; Yujie Zhou; Panfeng Wang; Siyan Zhan; et al. (International Archives of Occupational and Environmental Health, 2023)
Background and purpose Efforts to improve nurses’ physical and mental health are critical to ensuring the safety and quality of the healthcare system. Long-term studies targeting the relevancy of nurses’ occupation characteristics with health conditions remain insufficient. This study aimed to examine the relationship between nurses’ night shift and sleep problems and metabolic abnormalities risk. Methods This study was a part of the National Nurse Health Study, an ambispective cohort study in China, in 2021. Based on an integration physical examination data system, this study carried out a retrospective analysis of 730 nurses from 2018 to 2020 and combined with a questionnaire survey in 2021. The STROBE guidelines were adopted for reporting. Results In the 23 (23.0, 24.0) months follow-up, higher night shift load was associated with more sleep problems such as shortened sleep duration, sleep disorders, poor sleep quality, and sleep deprivation. Moreover, night shift load was associated with chronic diseases risk factors, increasing body mass index and body fat, with more night shift density, increasing the occurrence of low levels of high-density lipoprotein cholesterol, high triglyceride, triglyceride/high-density lipoprotein cholesterol ratio, and serum uric acid. Conclusion The night shift load has become an occupational health concern, contributing to chronic diseases relevant metabolic risk factors and negative influence on sleep health. Focus on the strategies to improve the sleep quality of nurses undergoing night shift work, optimize work scheduling and ongoing monitor the relevant risk factors are essential to enhance the stability and well-being of the nursing workforce. Clinical Trials registration information: NCT04572347, on October 1, 2020. https://www.clinicaltrials.gov/ct2/show/NCT04572347

Bibliometric and literature review of the development of mineral fertilizers - Zijie Gao; Lin Zhao; Hongzhi Geng; Mengxiao Li; Daying Chen; Youjun Zhang (Environmental Science and Pollution Research, 2023)

Fe-MOF-derived carbon compounds as catalysts for trichloroethylene degradation via persulfate oxidation: Role of precursor template and pyrolysis temperature - Jiashu Liu; Lin Zhao; Hongzhi Geng; Bin Wang; Xuejiao Tong; Yihan Li; Daying Chen; Peizhe Sun; Yongkui Yang (Journal of Environmental Chemical Engineering, 2023)

Ensemble machine learning reveals key structural and operational features governing ion selectivity of polyamide nanofiltration membranes - Dan Lu; Xuanchao Ma; Jiancong Lu; Yukun Qian; Yifang Geng; Jing Wang; Zhikan Yao; Lijun Liang; Zhilin Sun; Songmiao Liang; Lin Zhang (Desalination, 2023)

Unlocking ventilation flexibility of large airport terminals through an optimal CO2-based demand-controlled ventilation strategy - Hao Tang; Juan Yu; Yang Geng; Zhe Wang; Xue Liu; Zujian Huang; Borong Lin (Building and Environment, 2023)

The immune enhancement effect of CpG-ODNs on the vaccine of inactivated Vibrio harveyi in tiger puffer (Takifugu rubripes) - Simiao Yu; Lei Gao; Zhen Geng; Wei Wu; Xuejie Lin; Ruijun Li; Shigen Ye; Lingling Wang; Linsheng Song (Aquaculture, 2023)

Start-up mechanism of simultaneous nitrification-endogenous denitrification process for treatment of low C/N wastewater: Insights into reactor performance and microbial community dynamics - Daying Chen; Yongkui Yang; Hongzhi Geng; Danning Chen; Zhi Qiao; Meilin Yin; Xiaohui Wang; Lin Zhao (Journal of Cleaner Production, 2023)

Comprehensive renovation and optimization design of balconies in old residential buildings in Beijing: A study - Ning Li; Xufeng Miao; Wenying Geng; Ziwei Li; Lin Li (Energy and Buildings, 2023)

Effect of abnormal values of three temperature indicators on ischemic stroke hospital admissions in Guangzhou, China - Guobin Wang; Geng Lin; Fiona Fan Yang; Zhuoqing Wang (Journal of Thermal Biology, 2023)

Ethylene enhanced waterlogging tolerance by changing root architecture and inducing aerenchyma formation in maize seedlings - Shiying Geng; Ziqing Lin; Shipeng Xie; Jinzhong Xiao; Haiyan Wang; Xi Zhao; Yuyi Zhou; Liusheng Duan (Journal of Plant Physiology, 2023)

Remediation of soil polluted with Pb and Cd and alleviation of oxidative stress in Brassica rapa plant using nanoscale zerovalent iron supported with coconut-husk biochar - Moses Akintayo Aborisade; Hongzhi Geng; Belay Tafa Oba; Akash Kumar; Efomah Andrew Ndudi; Ashenafi Yohannes Battamo; Jiashu Liu; Daying Chen; Oluwaseun Princess Okimiji; Oluwasheyi Zacchaeus Ojekunle; Yongkui Yang; Peizhe Sun; et al. (Journal of Plant Physiology, 2023)

Industrial symbiosis promoting material exchanges in Ulan Buh Demonstration Eco-industrial Park: A multi-objective MILP model - Hao Yu; Lin Da; Yalun Li; Yanqiong Chen; Qingdan Geng; Zhibin Jia; Yun Zhang; Jinhua Li; Caixia Gao (Journal of Cleaner Production, 2023)

Compressive strength prediction of hydrothermally solidified clay with different machine learning techniques - Minguo Lin; Ruobin Su; Geng Chen; Yonghui Chen; Zi Ye; Nan Hu (Journal of Cleaner Production, 2023)

Mapping submarine landslides susceptibility in continental slopes with rich gas hydrates - Lin Tan; Fang Liu; Yu Huang; Rui Wang; Jianhua Geng; Giovanni Crosta; Paolo Frattini (Gas Science and Engineering, 2023)

A more accurate approach to estimate the C-factor of RUSLE by coupling stratified vegetation cover index in southern China - Geng Guo; Ying Pan; Jie Kuai; Qiao Dai; Yanfang Zhu; Yanyin Xu; Xichuan Jia; Guangruo Zeng; Jie Lin (Forest Ecology and Management, 2023)

Occurrence and migration of organophosphite and organophosphate esters into food simulants from single-use food packaging in China - Ruize Zhou; Jianqiang Geng; Jie Jiang; Li Lin; Jing Zhang; Yunjia Yang; Xiaojun Wang; Yumin Niu; Bing Shao (Environmental Pollution, 2023)

The model polysaccharide potato galactan is actually a mixture of different polysaccharides - Zhangkai Feng; Zhiying Lin; Huazhi Tang; Jie Geng; Yanbo Hu; Kevin H. Mayo; Guihua Tai; Yifa Zhou (Carbohydrate Polymers, 2023)

Softening/Hardening Damage Model and Numerical Implementation of Seabed Silt-Steel Interface in Yellow River Underwater Delta - Peng Yu; Honghua Liu; Lin Geng; Shuai Wang; Yang Yu; Chenghao Zhu; Qi Yang; Hongjun Liu; Yong Guan (Journal of Marine Science and Engineering, 2023)
The interaction between soil and structure is a research hotspot in ocean engineering, and the shear performance of interfaces is an essential factor affecting the bearing capacity of offshore structures. Taking the Yellow River Underwater Delta as the research area, the Softening/Hardening damage model of the silt–steel interface and the determination method of model parameters are proposed based on the statistical damage theory. Through the interface monotonic shear test under the conditions of different normal stress, roughness and water content, the shear mechanical properties and volumetric deformation laws on the silt–steel interface are analyzed, and the damage model parameters are obtained. Finally, a FRIC subroutine for the damage model was developed based on ABAQUS. The research results indicate the following: (1) The interface between silt and steel exhibits two characteristics, softening/hardening and shear shrinkage/expansion, under different conditions. Roughness significantly impacts interfacial cohesion, while water content mainly affects the internal friction angle. (2) The softening model based on the classic rock damage model can better simulate the stress–strain relationship of the silt–steel interface under high normal stress and low water content. In contrast, the hardening model based on the classic hyperbola model can better simulate the stress–strain relationship under low normal stress and high water content. The calculated results of the softening/hardening model agree with the experimental results, and the model has 7 parameters. (3) The developed FRIC subroutine can effectively simulate the nonlinear mechanical behavior of the interface between silt and steel. The research results provide a reference for exploring the stability analysis of offshore structures considering interface weakening effects.

Improved calculation method for consolidation of dredger fill treatment using prefabricated vertical-horizontal drains - Chen Geng; Minguo Lin; Chen Yonghui; Yanxiang Guo; Jing Wu; Ruobin Su (Marine Georesources & Geotechnology, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Effect of Arbuscular mycorrhizal fungi (AMF) inoculation on endophytic bacteria of lettuce - Zhixiang Han; Zihua Zhang; Yingyue Li; Boyan Wang; Qingchen Xiao; Zishan Li; Xiaowan Geng; Keqing Lin; Tao Huang; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2023)

Synergistic action of ferrate and biochar in the removal of trichloroethylene from water: Little biochar addition, large ferrate activity improvement - Yongkui Yang; Xiaoke Ma; Shaoyi Zhang; Xiao Luo; Hongzhi Geng; Jiashu Liu; Xuejiao Tong; Youjun Zhang; Peizhe Sun; Lin Zhao (Journal of Environmental Chemical Engineering, 2023)

Modification of low temperature-related hospital admissions for cardiovascular diseases by multiple green space indicators at multiple spatial scales: Evidence from Guangzhou, China - Guobin Wang; Fiona Fan Yang; Geng Lin; Zhuoqing Wang; Xiangxue Zhang (International Journal of Hygiene and Environmental Health, 2023)

Extremely weak Lg attenuation reveals ancient continental relicts in the South China block - Lin Shen; Lian-Feng Zhao; Xiao-Bi Xie; Geng Yang; Zhen-Xing Yao (Earth and Planetary Science Letters, 2023)

3D elastodynamic solutions to layered transversely isotropic soils considering the groundwater level - Zi Ye; Yonghui Chen; Gangqiang Kong; Geng Chen; Minguo Lin (Computers and Geotechnics, 2023)

Bifunctional lithiophilic carbon fibers with hierarchical structure for high-energy lithium metal batteries - Taiyu Lyu; Fenqiang Luo; Zhen Wang; Futing Jiang; Shize Geng; Yan Zhuang; Xin Lin; Junkai Chen; Dechao Wang; Lingzheng Bu; Lei Tao; Lizhe Liang; et al. (Chemical Engineering Journal, 2023)

Inchworm-Inspired soft robot with magnetic driving based on PDMS, EGaIn and NdFeB (PEN) combination - Yanfang Guan; Yansheng Liu; Qilong Wang; Hao Geng; Tangyong Cui; Yuang Hu; Qing Luo; Aonan Li; Wujie Li; Yang Lin; Lin Zhang; Guangyu Liu; et al. (Chemical Engineering Journal, 2023)

Response of soil erosion to vegetation restoration and terracing on the Loess Plateau - Peng Tian; Xiaojing Tian; Ren Geng; Guangju Zhao; Lin Yang; Xingmin Mu; Peng Gao; Wenyi Sun; Yulin Liu (CATENA, 2023)

Knowledge Map and Global Trends in Root Exudates Research from 2012 to 2021: a Bibliometric Analysis - Xin Zheng; Dongming Chen; Jiqiong Zhou; Qian Huang; Xingpeng Hu; Zhuxin Deng; Xuemei Fang; Feida Sun; Junming Zhao; Xiao Ma; Congyu Ma; Xinrui Yan; et al. (Journal of Soil Science and Plant Nutrition, 2023)

Investigation of physical and mechanical properties of clay soils around deep shafts - Yuansheng Lin; Zhen Huang; Zhenquan Jiang; Cong Gong; Kui Zhao; Qixiong Gu; Yufan Wu; Rui Zhang; Jiabo Geng (Bulletin of Engineering Geology and the Environment, 2023)

Spatiotemporal variations and impact factors of nutrients in the Sanya Bay, northern South China Sea - Xinxing Geng; Chuanliang Wu; Ziwei Yang; Junying Zhu; Kai Tang; Jiamin Lin; Yaxing Liu; Yufang Zhang; Mingxun An; Weibin Zhao; Yang Yu (Environmental Science and Pollution Research, 2023)

Effects on the migration and speciation of heavy metals by combined capping and biochemical oxidation during sediment remediation - Juan Lin; Mengling Liu; Sunling Zhuang; Bing Geng; Xiaodi Wang; Jiasheng Ma; Musong Chen (Science of The Total Environment, 2023)

Identification of the regulatory mechanism of ACE2 in COVID-19–induced kidney damage with systems genetics approach - Xueling Yang; Chunhua Lin; Jian Liu; Ya Zhang; Tingzhi Deng; Mengna Wei; Shuijing Pan; Lu Lu; Xuri Li; Geng Tian; Jia Mi; Fuyi Xu; et al. (Journal of Molecular Medicine, 2023)

Correcting antenna phase center effects to reconcile the code/phase bias products from the third IGS reprocessing campaign - Jihang Lin; Jianghui Geng; Zhe Yan; Salim Masoumi; Qiyuan Zhang (GPS Solutions, 2023)

Wetland soil carbon dioxide emission dynamics with external dissolved organic matter in mid–high-latitude forested watershed - Pengtao Wang; Wei Ouyang; Weihong Zhu; Fang Geng; Roberto Xavier Supe Tulcan; Chunye Lin (Agricultural and Forest Meteorology, 2023)

Tailoring the crumpled structures of a polyamide membrane with a heterostructural MXene-TiO2 interlayer for high water permeability - Jiawei Fu; Hang Xu; Tao Lin; Ao Wang; Anqi Wang; Chen Yao; Weihang Chen; Mingmei Ding; Chunxia Geng; Li Gao (Desalination, 2023)

Self-supply of H2O2 and O2 by a composite nanogenerator for chemodynamic therapy/hypoxia improvement and rapid therapy of biofilm-infected wounds - Junjie Wu; Peng Shen; Xian Qin; Yulu Yang; Chuanchuan Lin; Xuan Li; Wenbo Geng; Pengfei Gao; Lixue Chen; Li Miao; Yang Jiao; Bailong Tao (Chemical Engineering Journal, 2023)

No tillage outperforms conventional tillage under arid conditions and following fertilization - Stavros D. Veresoglou; Junjiang Chen; Xuheng Du; Qi Fu; QingLiu Geng; Chenyan Huang; Xilin Huang; Nan Hu; Yiming Hun; Guolin C. Li; Zhiman Lin; Zhiyu Ma; et al. (Soil Ecology Letters, 2023)

Origin and geological control of desorbed gas in multi-thin coal seam in the Wujiu depression, Hailar Basin, China - Geng Li; Yong Qin; Xuejuan Song; Boyang Wang; Haipeng Yao; Yabing Lin (Frontiers of Earth Science, 2023)

Highly selective adsorption of Hg (II) from aqueous solution by three-dimensional porous N-doped starch-based carbon - Chao Geng; Ruikang Lin; Peilin Yang; Pengfei Liu; Li Guo; Bo Cui; Yishan Fang (Environmental Science and Pollution Research, 2023)

Phytoplankton biomass dynamics with diffuse terrestrial nutrients pollution discharge into bay - Wei Ouyang; Rui Wang; Kaiyue Ji; Xitao Liu; Fang Geng; Xin Hao; Chunye Lin (Chemosphere, 2023)

Preparation of layered titanate nanosheets and the application for Cs+ adsorption from wastewater, effluents and a simulated brine - Wanlei Geng; Debin Wang; Yinfeng Liu; Jialing Zhang; Limei Zhong; Runxiong Lin; Li Ding; Lianying Wu; Dianquan Dong (Hydrometallurgy, 2023)

Engineering electron redistribution of bimetallic phosphates with CeO2 enables high-performance overall water splitting - Xin Guo; Menggang Li; Longyu Qiu; Fenyang Tian; Lin He; Shuo Geng; Yequn Liu; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2023)

Short-term ambient particulate matter pollution of different sizes and respiratory hospital admission in the Beibu Gulf area of Southern China - Haopeng Li; Lizhong Liang; Shiyu Zhang; Zhengmin (Min) Qian; Miao Cai; Xiaojie Wang; Stephen Edward McMillin; Amy E. Keith; Jing Wei; Yan Geng; Hualiang Lin (Atmospheric Environment, 2023)

Dynamic mechanical behavior and macroscopic and microscopic characteristics of granites subject to heating treatment - Yanbing Wang; Lin Luo; Jianlei Chen; Zhen Liu; Yanjie Geng (Arabian Journal of Geosciences, 2023)

Combined effects of prenatal phthalate exposure on cardiometabolic risk score among 4- to 7-year-old children: MABC study - Hui Gao; Meng-long Geng; Juan Tong; Bao-lin Wang; Kun Huang; Yi Zhang; Hong Gan; Bei-bei Zhu; Peng Ding; Qu-nan Wang; Jian-qing Wang; Cheng Zhang; et al. (Chemosphere, 2023)

Rapid identification of fish species by laser-induced breakdown spectroscopy and Raman spectroscopy coupled with machine learning methods - Lihui Ren; Ye Tian; Xiaoying Yang; Qi Wang; Leshan Wang; Xin Geng; Kaiqiang Wang; Zengfeng Du; Ying Li; Hong Lin (Food Chemistry, 2023)

Interactions between kafirin and pickle-like odorants in soy sauce flavor Baijiu: Aroma profile change and binding mechanism - Lin Zhu; Xuebo Song; Xing Li; Xiaojie Geng; Fuping Zheng; Hehe Li; Jinyuan Sun; Mingquan Huang; Baoguo Sun (Food Chemistry, 2023)

An ultra-sensitive and specific nanoplasmonic-enhanced isothermal amplification platform for the ultrafast point-of-care testing of SARS-CoV-2 - Juxiang Liu; Ping Chen; Xulong Hu; Liping Huang; Zhi Geng; Hao Xu; Wenjun Hu; Lin Wang; Ping Wu; Gang L. Liu (Chemical Engineering Journal, 2023)

Associations of trace element levels in paired serum, whole blood, and tissue: an example of esophageal squamous cell carcinoma - Kexin Cao; Jingbing Zhang; Geng Wang; Xiaosheng Lin; Fulan Zhan; Kusheng Wu; Wei Tan; Hui Geng; Caixia Liu (Environmental Science and Pollution Research, 2022)

Mechanism of simultaneous lead and chromium removal from contaminated wastewater by a schwertmannite-like mineral - Mingyan Shi; Yali Zhang; Weibin Hong; Jiayu Liu; Huijie Zhu; Xu Liu; Yuxin Geng; Zhenyin Cai; Shaonan Lin; Chengzhi Ni (Environmental Science and Pollution Research, 2022)

Identification of the Hub Genes and the Signaling Pathways in Human iPSC-Cardiomyocytes Infected by SARS-CoV-2 - Li-Min Xie; Yin-Fei Huang; Ye-Ling Liu; Jia-Qi Liang; Wei Deng; Geng-Ling Lin; Huan-Min Luo; Xu-Guang Guo (Biochemical Genetics, 2022)

Recent development in zebrafish model for bioactivity and safety evaluation of natural products - Fang-Jun Lin; Hang Li; Ding-Tao Wu; Qi-Guo Zhuang; Hua-Bin Li; Fang Geng; Ren-You Gan (Critical Reviews in Food Science and Nutrition, 2022)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

The fibroblast growth factor receptor antagonist SSR128129E inhibits fat accumulation via suppressing adipogenesis in mice - Xinzhi Zhang; Xin Wen; Geng Hu; Qiang Zhang; Qianying Sun; Yanxin Jia; Yan Liu; Hai Lin; Haifang Li (Molecular Biology Reports, 2022)

Polyethylene microplastic exposure and concurrent effect with Aeromonas hydrophila infection on zebrafish - Ning Ding; Lin Jiang; Xiao Wang; Chun Wang; Yue Geng; Jianxin Zhang; Yingxue Sun; Yanping Zhang; Quan Yuan; Hong Liu (Environmental Science and Pollution Research, 2022)

Stabilization of coarse-grained saline soil using microbially enhanced calcium carbonate deposition - Shengyi Cong; Liang Tang; Bo Wang; Xianzhang Ling; Lin Geng; Wenqiang Xing (Bulletin of Engineering Geology and the Environment, 2022)

Gestational exposure to PCB-118 impairs placental angiogenesis and fetal growth - Caiyun Ge; Ting Geng; Lin Cheng; Yuanzhen Zhang (Environmental Science and Pollution Research, 2022)

Secretory phospholipase A2 group XIIBs play potential roles in intestine antibacterial responses in seahorse - Wanghong Xiao; Geng Qin; Yanhong Zhang; Bo Zhang; Tao Li; Zelin Chen; Qiang Lin (Journal of Fish Diseases, 2022)

Cerebellar Oscillations in Familial and Sporadic Essential Tremor - Shi-Bing Wong; Yi-Mei Wang; Chih-Chun Lin; Scott Kun Geng; Nora Vanegas-Arroyave; Seth L. Pullman; Sheng-Han Kuo; Ming-Kai Pan (The Cerebellum, 2022)

Characterizing sediment bacterial community and identifying the biological indicators in a seawater-freshwater transition zone during the wet and dry seasons - Yongbin Li; Duanyi Huang; Weimin Sun; Xiaoxu Sun; Geng Yan; Wenlong Gao; Hanzhi Lin (Environmental Science and Pollution Research, 2022)

Genome-wide analysis of the rose (Rosa chinensis) NAC family and characterization of RcNAC091 - Lifang Geng; Lin Su; Lufeng Fu; Shang Lin; Jianmei Zhang; Qinghua Liu; Xinqiang Jiang (Plant Molecular Biology, 2022)

Genome-wide analysis of BURP genes and identification of a BURP-V gene RcBURP4 in Rosa chinensis - Lufeng Fu; Zhujun Zhang; Hai Wang; Xiaojuan Zhao; Lin Su; Lifang Geng; Yizeng Lu; Boqiang Tong; Qinghua Liu; Xinqiang Jiang (Plant Cell Reports, 2022)

Transcriptome Analysis Reveals Molecular Mechanisms Underlying Methyl Jasmonate-mediated Biosynthesis of Protopanaxadiol-type Saponins in Panax notoginseng Leaves - Ying Li; Yuan Lin; Bing Jia; Geng Chen; Huineng Shi; Rui Xu; Xuejiao Li; Junrong Tang; Qingyan Tang; Guanghui Zhang; Jianli Yang; Wei Fan; et al. (Journal of Plant Biology, 2022)

The lining responses for shallow mountain tunnels subjected to frost heaving - Xian-zhang Ling; Yuan Yu; Liang Tang; Lin Geng; Xiao Han (Journal of Mountain Science, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)

Verification of Real-Time Microbial Monitoring Technology Based on the Principle of Laser-Induced Fluorescence Under USP <1223> Standard and Prospective Application in Our Hospital PIVAS Clean Room - Zhou Geng; Wenbin Yang; Shubo Wei; Lin Wang; Jie Pan (International Journal of Peptide Research and Therapeutics, 2022)

Analysis of the thaumatin-like genes of Rosa chinensis and functional analysis of the role of RcTLP6 in salt stress tolerance - Lin Su; Xiaojuan Zhao; Lifang Geng; Lufeng Fu; Yizeng Lu; Qinghua Liu; Xinqiang Jiang (Planta, 2021)

Wnt8a is one of the candidate genes that play essential roles in the elongation of the seahorse prehensile tail - Bo Zhang; Geng Qin; Lili Qu; Yanhong Zhang; Chunyan Li; Chunlei Cang; Qiang Lin (Marine Life Science & Technology, 2021)

Postnatal development of BAG3 expression in mouse cerebral cortex and hippocampus - Xinlu Li; Geng Lin; Tongtong Liu; Ning Zhao; He Xu; Huaqin Wang; Wei Zheng (Brain Structure and Function, 2021)

Numerical Investigation of the Characteristics of Erosion in a Centrifugal Pump for Transporting Dilute Particle-Laden Flows - Rui-Jie Zhao; You-Long Zhao; De-Sheng Zhang; Yan Li; Lin-Lin Geng (Journal of Marine Science and Engineering, 2021)
Erosion in centrifugal pumps for transporting flows with dilute particles is a main pump failure problem in many engineering processes. A numerical model combining the computational fluid dynamics (CFD) and Discrete Element Method (DEM) is applied to simulate erosion in a centrifugal pump. Different models of the liquid-solid inter-phase forces are implemented, and the particle-turbulence interaction is also defined. The inertial particles considered in this work are monodisperse and have finite size. The numerical results are validated by comparing the results with a series of experimental data. Then, the effects of particle volume fraction, size, and shape on the pump erosion are estimated in the simulations. The results demonstrate that severe erosive areas are located near the inlet and outlet of the pressure side of the impeller blade, the middle region of the blade, the corners of the shroud and hub of the impeller adjoining to the pressure side of the blade, and the volute near the pump tongue. Among these locations, the maximum erosion occurs near the inlet of the pressure side of the blade. Erosion mitigation occurs under the situation where more particles accumulate in the near-wall region of the eroded surface, forming a buffering layer. The relationship between the particle size and the erosion is nonlinear, and the 1 mm particle causes the maximum pump erosion. The sharp particles cause more severe erosion in the pump because both the frequency of particle-wall collisions and the impact angle increase with the increasing sharpness of the particle.

Enhancement of sludge dewaterability by a magnetic field combined with coagulation/flocculation: a comparative study on municipal and citric acid–processing waste-activated sludge - Ning Ding; Xiao Wang; Lin Jiang; Jianxin Zhang; Yue Geng; Liming Dong; Hong Liu (Environmental Science and Pollution Research, 2021)

Serum macrophage migration inhibitory factor as a potential biomarker to evaluate therapeutic response in patients with allergic asthma: an exploratory study - Huiyuan Zhu; Shaochun Yan; Jingshuo Wu; Zhong Zhang; Xiaolin Li; Zheng Liu; Xing Ma; Lina Zhou; Lin Zhang; Mingming Feng; Yiwei Geng; Aixin Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Non-linear relationships and interactions of meteorological factors on mumps in Jinan, China - Shaoqian Lin; Shiman Ruan; Xingyi Geng; Kaijun Song; Liangliang Cui; Xiaoxue Liu; Yingjian Zhang; Meng Cao; Ying Zhang (International Journal of Biometeorology, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Paleoglacial and paleoclimate reconstructions during the global Last Glacial Maximum in the Longriba area, eastern Tibetan Plateau - Wei-lin Yang; Ye-song Han; Xu Peng; Ze-ze Ran; Qing Liu; Geng-nian Liu (Journal of Mountain Science, 2021)

Overexpression of a tonoplast Na+/H+ antiporter from the halophytic shrub Nitraria sibirica improved salt tolerance and root development in transgenic poplar - Xin Geng; Shouye Chen; E. Yilan; Wenbo Zhang; Huiping Mao; Alatan qiqige; Yingchun Wang; Zhi Qi; Xiaofei Lin (Tree Genetics & Genomes, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Xanthatin mediates G 2 /M cell cycle arrest, autophagy and apoptosis via ROS/XIAP signaling in human colon cancer cells - Ya-di Geng; Lei Zhang; Guo-Yu Wang; Xiao-Jun Feng; Zhao-Lin Chen; Ling Jiang; Ai-Zong Shen (Natural Product Research, 2020)

Functional analysis of miR-767-5p during the progression of hepatocellular carcinoma and the clinical relevance of its dysregulation - Lei Zhang; Zhimin Geng; Yong Wan; Fandi Meng; Xiankui Meng; Lin Wang (Histochemistry and Cell Biology, 2020)

Endometrial autophagy is essential for embryo implantation during early pregnancy - Yan Su; Juan-Juan Zhang; Jun-Lin He; Xue-Qing Liu; Xue-Mei Chen; Yu-Bin Ding; Chao Tong; Chuan Peng; Yan-Qing Geng; Ying-Xiong Wang; Ru-Fei Gao (Journal of Molecular Medicine, 2020)

Dynamic Detection of Thrombolysis in Embolic Stroke Rats by Synchrotron Radiation Angiography - Liping Wang; Panting Zhou; Zhihao Mu; Xiaojie Lin; Lu Jiang; Zhuo Cheng; Longlong Luo; Zhiming Xu; Jieli Geng; Yongting Wang; Zhijun Zhang; Guo-Yuan Yang (Translational Stroke Research, 2019)

A changed post‐flood management strategy enables the culture‐based fishery of the Liangzi Lake, Yangtze River Basin, China, to remain economically and environmentally viable - Qidong Wang; Zhongjie Li; Mingli Lin; Shaowe Ye; Wei Li; Chuanbo Guo; Geng Huang; Jing Yuan; Jiashou Liu; Sena S. De Silva (Fisheries Management and Ecology, 2019)
The culture‐based fishery of Liangzi Lake, Yangtze River Basin, established in 1992, yielded 2,652 t/year (±167) between 2005 and 2015, dominated by stocked carps [ Hypophthalmichthys molitrix (Val.) and Hypophthalmichthys nobilis (Richardson)] and mitten crab Eriocheir sinensis (Milne Edwards), accounting for 53% and 23% of the production and 20% and 52% in value, respectively. The lake had a macrophyte cover dominated by Vallisneria natans (Lour.) Hara with a cumulative biomass of 10,647 g/m 2 that disappeared after a major flood in 2010 and changed its ecology. Management changes in stocking strategies introduced in the post‐flood period enabled the culture‐based fishery to maintain viability and sustainability to combat the major ecological change in the lake. The stocked species contributed significantly to nutrient removal of 24.71 ± 5.12 t/yr and 6.29 ± 0.87 t/yr of total nitrogen and total phosphorus, respectively.

Inhibition of Neointima Hyperplasia, Inflammation, and Reactive Oxygen Species in Balloon-Injured Arteries by HVJ Envelope Vector-Mediated Delivery of Superoxide Dismutase Gene - Shoa-Lin Lin; Jwu-Lai Yeh; Pei-Chia Tsai; Tsung-Hsien Chang; Wei-Chun Huang; Song-Tay Lee; Michael Wassler; Yong-Jian Geng; Erna Sulistyowati (Translational Stroke Research, 2019)

TLR2 gene in seahorse brood pouch plays key functional roles in LPS‐induced antibacterial responses - Bo Zhang; Huixian Zhang; Geng Qin; Yuhong Liu; Xue Han; Jianping Yin; Qiang Lin (Journal of Fish Diseases, 2019)

Association analysis between feed efficiency and expression of key genes of the avTOR signaling pathway in meat-type ducks - Lei Yang; Tingting He; Yuan Xu; He Zang; Jiafa Wang; Zhiqiang Lin; Sihua Jin; Zhaoyu Geng (Molecular Biology Reports, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Comparison of Inorganic and Organically Bound Trace Minerals on Tissue Mineral Deposition and Fecal Excretion in Broiler Breeders - Geng Wang; Lujie Liu; Zhongpei Wang; Xun Pei; Wenjing Tao; Zhiping Xiao; Bojing Liu; Minqi Wang; Gang Lin; Tuoying Ao (Biological Trace Element Research, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Cover Image - Geng Qin; Yuan Zhang; Bo Zhang; Xin Wang; Jianping Yin; Qiang Lin (Journal of Fish Diseases, 2018)

Seahorse TLR 5 gene responses to Vibrio vulnificus infection, which in combination with scuticociliates causes heavy reductions in seahorse aquaculture - Geng Qin; Yuan Zhang; Bo Zhang; Xin Wang; Jianping Yin; Qiang Lin (Journal of Fish Diseases, 2018)

Microphytoplankton community structure in the western Arctic Ocean: surface layer variability of geographic and temporal considerations in summer - Yu Wang; Peng Xiang; Jian-hua Kang; You-yin Ye; Geng-ming Lin; Qing-liang Yang; Mao Lin (Hydrobiologia, 2018)

Comparative transcriptome analysis of Apis mellifera antennae of workers performing different tasks - Hongyi Nie; Shupeng Xu; Cuiqin Xie; Haiyang Geng; Yazhou Zhao; Jianghong Li; Wei-fone Huang; Yan Lin; Zhiguo Li; Songkun Su (Molecular Genetics and Genomics, 2018)

Tension force-induced bone formation in orthodontic tooth movement via modulation of the GSK-3β/β-catenin signaling pathway - Yelin Mao; Liangliang Wang; Ye Zhu; Yu Liu; Hongwei Dai; Jianping Zhou; Dechun Geng; Lin Wang; Yong Ji (Journal of Molecular Histology, 2018)

Analysis of miRNA-seq combined with gene expression profile reveals the complexity of salinity stress response in Oryza sativa - Qingwei Wang; Tianlong Geng; Shuhua Zhu; Rui Li; Yongao Tong; Shenghua Wang; Fang Chen; Lin Tang; Yang He (Acta Physiologiae Plantarum, 2017)

Composites ZSM-5/KIT-6 Synthesized Via Assembly Modification Procedure and Mechanical Grinding Procedure, Respectively, and Their Application to CO2 Adsorption - Zhifeng Lin; Jianwen Wei; Linlin Geng; Dejun Mei; Lei Liao (Water, Air, & Soil Pollution, 2017)

Down-Regulation of Neuregulin1/ErbB4 Signaling in the Hippocampus Is Critical for Learning and Memory - Jia Tian; Fei Geng; Feng Gao; Yi-Hua Chen; Ji-Hong Liu; Jian-Lin Wu; Yu-Jie Lan; Yuan-Ning Zeng; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Molecular Neurobiology, 2017)

Responses of root exudation and nutrient cycling to grazing intensities and recovery practices in an alpine meadow: An implication for pasture management - Geng Sun; Xia Zhu-Barker; Dongming Chen; Lin Liu; Nannan Zhang; Changguang Shi; Liping He; Yanbao Lei (Plant and Soil, 2017)

Intelligent diagnosis of jaundice with dynamic uncertain causality graph model - Shao-rui Hao; Shi-chao Geng; Lin-xiao Fan; Jia-jia Chen; Qin Zhang; Lan-juan Li (Journal of Zhejiang University-SCIENCE B, 2017)

Bagasse Activated Carbon with TETA/TEPA Modification and Adsorption Properties of CO2 - Jianwen Wei; Zhifeng Lin; Zeyu He; Linlin Geng; Lei Liao (Water, Air, & Soil Pollution, 2017)

miR-137 and miR-491 Negatively Regulate Dopamine Transporter Expression and Function in Neural Cells - Xiaojian Jia; Feng Wang; Ying Han; Xuewen Geng; Minghua Li; Yu Shi; Lin Lu; Yun Chen (Neuroscience Bulletin, 2016)

Paleokarst system based on FMI facies analysis: a case study in the Yingshan Formation at the Tazhong uplift in the Tarim Basin, Northwest China - Xiaojie Geng; Changsong Lin; Bin Wu; Hao Li (Arabian Journal of Geosciences, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

On the control of Microcystis aeruginosa and Synechococccus species using an algicidal bacterium, Stenotrophomonas F6, and its algicidal compounds cyclo-(Gly-Pro) and hydroquinone - Shengqin Lin; Mengxin Geng; Xianglong Liu; Jing Tan; Hong Yang (Journal of Applied Phycology, 2016)

Effect of Initial Stress on a Fiber-Reinforced Thermoelastic Porous Media Without Energy Dissipation - Qi-lin Xiong; Xiao-geng Tian (Transport in Porous Media, 2016)

Heat-induced unfolding of apo-CP43 studied by fluorescence spectroscopy and CD spectroscopy - Qing-Jie Xiao; Zai-Geng Li; Jiao Yang; Qing He; Lei Xi; Lin-Fang Du (Photosynthesis Research, 2015)

Combined effect of ligament stem cells and umbilical-cord-blood-derived CD34+ cells on ligament healing - Dapeng Jiang; Shulong Yang; Peng Gao; Yubo Zhang; Tieyun Guo; Houwei Lin; Hongquan Geng (Cell and Tissue Research, 2015)

Swine and rabbits are the main reservoirs of hepatitis E virus in China: detection of HEV RNA in feces of farmed and wild animals - Junke Xia; Hang Zeng; Lin Liu; Yulin Zhang; Peng Liu; Jiabao Geng; Lin Wang; Ling Wang; Hui Zhuang (Archives of Virology, 2015)

VEGF-Loaded Nanoparticle-Modified BAMAs Enhance Angiogenesis and Inhibit Graft Shrinkage in Tissue-Engineered Bladder - Xincheng Jiang; Qianwei Xiong; Guofeng Xu; Houwei Lin; Xiaoliang Fang; Daxiang Cui; Maosheng Xu; Fang Chen; Hongquan Geng (Annals of Biomedical Engineering, 2015)

Lipophilic shellfish toxins in Dinophysis caudata picked cells and in shellfish from the East China Sea - Aifeng Li; Geng Sun; Jiangbing Qiu; Lin Fan (Environmental Science and Pollution Research, 2015)

The phytotoxin coronatine is a multifunctional component of the virulence armament of Pseudomonas syringae - Xueqing Geng; Lin Jin; Mikiko Shimada; Min Gab Kim; David Mackey (Planta, 2014)

Sorafenib Inhibition of Hepatic Stellate Cell Proliferation in Tumor Microenvironment of Hepatocellular Carcinoma: A Study of the Sorafenib Mechanisms - Zhi-min Geng; Rajiv Kumar Jha; Bo Li; Chen Chen; Wen-zhi Li; Jian-bao Zheng; Lin Wang; Sha Huanchen (Cell Biochemistry and Biophysics, 2014)

Unpalatable weed Stellera chamaejasme L. provides biotic refuge for neighboring species and conserves plant diversity in overgrazing alpine meadows on the Tibetan Plateau in China - Wei Cheng; Geng Sun; Lin-fang Du; Yan Wu; Qun-ying Zheng; Hong-xuan Zhang; Lin Liu; Ning Wu (Journal of Mountain Science, 2014)

Transgenic maize lines expressing a cry1C* gene are resistant to insect pests - Dengxiang Du; Cunjuan Geng; Xiaobo Zhang; Zuxin Zhang; Yonglian Zheng; Fangdong Zhang; Yongjun Lin; Fazhan Qiu (Plant Molecular Biology Reporter, 2014)

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Age-dependent down-regulation of DNA polymerase δ1 in human lymphocytes - Jin-Ling Wang; Hong-Lin Guo; Pei-Chang Wang; Chen-Geng Liu (Molecular and Cellular Biochemistry, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Dissipation and Residue Determination of Fluoroglycofen-Ethyl in Soybean and Soil by UPLC-MS–MS - Yue Geng; Ran Jia; Chongjiu Li; Xiaodong Ma; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Analysis of genetic variations in the dopamine D1 receptor (DRD1) gene and antipsychotics-induced tardive dyskinesia in schizophrenia - I-Ching Lai; Geng-Han Mo; Mao-Liang Chen; Ying-Chieh Wang; Jen-Yeu Chen; Ding-Lieh Liao; Ya-Mei Bai; Chao-Cheng Lin; Tzu-Ting Chen; Ying-Jay Liou (European Journal of Clinical Pharmacology, 2011)

Temporal and spatial variability of chlorophyll a concentration in Lake Taihu using MODIS time-series data - Yuchao Zhang; Shan Lin; Xin Qian; Qin’geng Wang; Yu Qian; Jianping Liu; Yi Ge (Hydrobiologia, 2011)

Prognostic significance of survivin expression in renal cell cancer and its correlation with radioresistance - Yu Lei; Zhang Geng; Wu Guo-Jun; Wang He; Yuan Jian-Lin (Molecular and Cellular Biochemistry, 2010)

Social construction functions of consumption space under stratification: The case of Guangzhou - Geng Lin; Lianjun Wang; Xiaoying Zhang (Chinese Geographical Science, 2010)

Protective Effect of Sulforaphane on Human Vascular Endothelial Cells Against Lipopolysaccharide-Induced Inflammatory Damage - Yujuan Shan; Ruifang Zhao; Wei Geng; Na Lin; Xiaoxue Wang; Xiaoyan Du; Shuran Wang (Cardiovascular Toxicology, 2010)

The effects of mesenchymal stem cells on c-kit up-regulation and cell-cycle re-entry of neonatal cardiomyocytes are mediated by activation of insulin-like growth factor 1 receptor - Xi-Yong Yu; Yong-Jian Geng; Xiao-Hong Li; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yao-Hua Song; Yangxin Li (Molecular and Cellular Biochemistry, 2009)

Functional analysis of a putative regulatory gene, tadR, involved in aniline degradation in Delftia tsuruhatensis AD9 - Lizhao Geng; Ming Chen; Quanfeng Liang; Wei Liu; Wei Zhang; Shuzhen Ping; Wei Lu; Yongliang Yan; Weiwei Wang; Masahiro Takeo; Min Lin (Archives of Microbiology, 2009)

A new labdane type diterpenoid from Trollius ledebouri - Jian-Hua Zou; Jun-Shan Yang; Liang Zhou; Geng Lin (Natural Product Research, 2006)

Apoptotic and anti-proliferative effects of 17β-estradiol and 17β-estradiol-like compounds in the Hep3B cell line - Erh-Jung Huang; Cheng-Chung Wu; Hsien-Ping Huang; Jer-Yuh Liu; Chung-Sheng Lin; Yan-Zin Chang; James A. Lin; Jaung-Geng Lin; Li-Mien Chen; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

Energy flux, body size and density in relation to bird species richness along an elevational gradient in Taiwan - Tzung‐Su Ding; Hsiao‐Wei Yuan; Shu Geng; Yao‐Sung Lin; Pei‐Fen Lee (Global Ecology and Biogeography, 2005)
Aim To examine the species richness of breeding birds along a local elevational gradient and to test the following assumptions of the energy limitation hypothesis: (1) the energy flux through birds is positively correlated with above‐ground net primary productivity, (2) bird density is positively correlated with total energy flux, and (3) bird species richness is positively correlated with bird density. Location An elevational gradient from 1400 to 3700 m on Mt. Yushan, the highest mountain in Taiwan (23°28′30″ N, 120°54′00″ E), with a peak of 3952 m a.s.l. Methods We established 50 sampling stations along the elevational gradient. From March to July 1992, we estimated the density of each bird species using the variable circular‐plot method. Above‐ground net primary productivity was modelled using monthly averages from weather data for the years 1961–90. Results Bird species richness had a hump‐shaped relationship with elevation and with net primary productivity. Bird energy flux was positively correlated with net primary productivity and bird species richness was positively correlated with bird density. The relationship between bird density and energy flux was hump‐shaped, which does not support one assumption of the energy limitation hypothesis. Main conclusions The results supported two essential assumptions of the energy limitation hypothesis. However, when energy availability exceeded a certain level, it could decrease species richness by increasing individual energy consumption, which reduced bird density. Thus, energy availability is a primary factor influencing bird species richness at this scale, but other factors, such as body size, could also play important roles.

Evaluation of Genotoxicity of Combined Pollution by Cadmium and Atrazine - A. J. Lin; Y. G. Zhu; Y. P. Tong; C. N. Geng (Bulletin of Environmental Contamination and Toxicology, 2005)

Effects of host stages and temperature on population parameters of Oomyzus sokolowskii, a larval-pupal parasitoid of Plutella xylostella - Xin-geng Wang; Shu-sheng Liu; Shi-jian Guo; Wen-cai Lin (BioControl, 1999)